Detachment primer composition and printed matter
The desorption primer composition with polyethyleneimine compounds and silane coupling agents addresses the challenge of bonding and separating printed layers from plastic laminates, ensuring reliable adhesion and easy detachment while reducing microplastic pollution.
Patent Information
- Application Number
- JP2024135515
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-29
- Filing Date
- 2024-08-15
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2042-09-14
AI Technical Summary
Existing methods for separating printed layers from plastic-based laminates are inadequate, leading to insufficient lamination suitability and residual adhesive on the film, and there is a need for a reliable method to bond and detach layers without environmental harm from microplastics.
A desorption primer composition is used comprising polyethyleneimine compounds with specific amine values and silane coupling agents, forming a release primer layer between the resin base material and the printing layer, facilitating easy separation of the printed layer from the base material using a desorption liquid.
The solution ensures reliable bonding during use and easy separation of the printed layer after use, effectively detaching the adhesive layer from the base film, reducing microplastic pollution by enhancing lamination suitability and detachment efficiency.
Smart Images

Figure 0007620761000001 
Figure 0007620761000002 
Figure 0007620761000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a release primer composition and a printed matter. [Background technology]
[0002] Packaging materials using various plastic films are used for food, confectionery, household goods, pet food, etc., from the viewpoints of design, economy, content protection, transportability, etc. Furthermore, gravure printing or flexographic printing is applied to many packaging materials with the intention of adding designs and messages that will appeal to consumers. In order to obtain these packaging materials, printing is performed by printing directly onto the surface of the base film of the packaging material, or by applying an adhesive or anchor agent to the printed surface printed on the surface of the base film of the packaging material as necessary and laminating the film. In printing for laminating a film, a colored ink composition and a white ink composition are printed in sequence on various films such as polyester, nylon, and aluminum foil, and then a polyethylene film or polypropylene film for heat sealing is laminated on the printed layer of the white ink composition by dry lamination using an adhesive or extrusion lamination using an anchor coating agent (see Patent Document 1).
[0003] In recent years, packaging made from plastic film, plastic bottles, and other plastic products have been discarded and dumped into the ocean as garbage, causing environmental pollution. These plastic products break down in seawater and become submicron-sized fragments (microplastics), which float in the seawater. If marine organisms such as fish ingest this plastic, it will accumulate in their bodies. This could have an impact on the health of seabirds and humans who consume the marine organisms as food.
[0004] As one of various efforts to reduce microplastics in order to improve such problems, a recycling method has been proposed in which the plastic substrate of a laminate is removed from a laminate in which a printing ink composition is laminated. As a method for removing the plastic substrate of a laminate, a removing ink composition (e.g., see Patent Document 2), a removing adhesive (e.g., see Patent Document 3), a removing anchor coating agent, etc. (e.g., see Patent Documents 4 to 6), and a removing liquid (e.g., see Patent Document 7) have been proposed. However, in these methods, the use of hot water as a release liquid is not sufficient for desorption, and when used in a laminate printing ink composition, there is a problem in that the lamination suitability is insufficient. There is also a laminate in which an adhesive is applied to a base film, and a paper base is bonded to the laminate to form a laminate on which printing is performed on the paper base side. However, this has the problem that the adhesive remains on the base film even after the paper base is removed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 5-97959 [Patent Document 2] Patent No. 6631964 [Patent Document 3] Patent No. 6642688 [Patent Document 4] Patent No. 6388131 [Patent Document 5] JP 2020-175620 A [Patent Document 6] International Publication No. 2021 / 090690 [Patent Document 7] Patent No. 6690806 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention aims to provide a method for bonding a substrate and a printed layer reliably during use, and to easily separate the printed layer from the substrate after use, and to easily separate the printed layer from a release liquid thereafter. Another object of the present invention is to provide a method for easily separating and removing an adhesive layer from a substrate film of a laminate in which a paper substrate is laminated to a substrate film via an adhesive layer. [Means for solving the problem]
[0007] The present inventors have found that the above problems can be solved by using the following removal primer composition and printed matter, and have arrived at the present invention. 1. For forming a removable primer layer on a printed material in which a resin substrate, a removable primer layer, and a printed layer are formed in this order, A release primer composition for a resin substrate and a printed layer, the composition comprising any one of A to B below: A. A polyethyleneimine compound having an amine value of 5.0 to 25.0 mmol / g (not B below) B. A polyethyleneimine compound having an amine value of 5.0 to 25.0 mmol / g, and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent, The ratio of the number of amino groups in the polyethyleneimine compound to the sum of the number of glycidyl groups and the number of isocyanate groups in the silane coupling agent is 0 to 2.50. (However, excluding coating solutions containing at least one binder resin, crosslinking agent, and polyethyleneimine, Furthermore, coating agents containing a water-soluble acrylic resin and a polyalkyleneimine are excluded.) 2. The primer composition for detachment of a resin substrate and a printed layer according to 1, wherein the polyethyleneimine compound or siloxane-modified polyethyleneimine compound has a number average molecular weight of 1,000 to 200,000. 3. The primer composition for detachment of a resin substrate and a printed layer according to 1, wherein the polyethyleneimine compound or siloxane-modified polyethyleneimine compound has a mass average molecular weight of 4,000 to 800,000. 4. The detachment primer composition according to 1 or 2, wherein the polyethyleneimine compound or siloxane-modified polyethyleneimine compound has a number average molecular weight of 1,000 to 200,000. 5. The detachment primer composition according to 1 or 2, wherein the polyethyleneimine compound or the siloxane-modified polyethyleneimine compound has a mass average molecular weight of 4,000 to 800,000. 6. A printed matter comprising a detachable primer layer formed from the detachable primer composition according to any one of 1 to 5 on a resin substrate, and a printed layer formed on the detachable primer layer. 7. A printed matter comprising: a detachable primer layer formed from the detachable primer composition described in any one of 1 to 5 on a resin substrate; a paper layer formed on the detachable primer layer via an adhesive layer; and a printed layer formed on the paper layer. Effect of the Invention
[0008] According to the present invention, the substrate and the printed layer can be reliably bonded during use, and the printed layer can be more easily separated from the substrate after use, and the printed layer can be easily separated from the release liquid after use. Furthermore, according to the present invention, the adhesive layer can be more easily separated from the substrate film of a laminate in which a paper substrate is laminated to a substrate film via an adhesive layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention is based on the following items and can be used for various printing methods and printed matter for various purposes. In the present specification, the release primer composition of the present invention may be simply referred to as the "primer composition". The present invention is significant in that a layer having a specific composition is used as the release primer layer.
[0010] [Removal primer composition] The detachment primer composition of the present invention is a composition for forming a primer layer that is provided so as to be positioned between the surface of a resin substrate and a printed layer. The detachment primer composition is used to separate a resin film or the like that is a substrate for a printed material from a printed layer formed thereon when the printed material is reused after use, and to detach the printed layer from the substrate. The detachment primer composition may be either an aqueous or oil-based composition. Since the present invention is a detachment primer composition, its use and desired properties differ from those of an anchor coating agent used, for example, when an anchor coating layer is further formed on a printed surface formed on a substrate and a resin film or the like is laminated thereon. The present invention is a composition for forming a primer layer on a printing substrate before printing with a printing ink composition. As the detachment primer composition, a polyethyleneimine-based compound having an amine value of 5.0 to 25.0 mmol / g can be used. In the present invention, the polyethyleneimine-based compound is A. a polyethyleneimine compound, B. a mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent, and C. a siloxane-modified polyethyleneimine compound. Note that when A to C are included, the term "polyethyleneimine-based compound" is used, and a compound included in the "polyethyleneimine-based compound" is used, for example, as a "polyethyleneimine compound." In the case of lamination, the polyethyleneimine compound and the siloxane-modified polyethyleneimine compound contained in the primer composition of the present invention preferably have a number average molecular weight of 1,000 to 200,000 from the viewpoint of strength. Among them, a number average molecular weight of 2,000 or more is preferable, and a number average molecular weight of 5,000 or more is more preferable. Also, a number average molecular weight of 200,000 or less is preferable. The polyethyleneimine compound and the siloxane-modified polyethyleneimine compound preferably have a mass average molecular weight of 4,000 to 800,000. Furthermore, a polyethyleneimine-based compound having all of the amino groups in the molecule, from primary amino groups to tertiary amino groups, is preferred, and among these, in terms of the content based on the number of each amino group, it is preferred that the secondary amino groups are contained in greater numbers than the primary and tertiary amino groups, and further it is more preferred that the content of secondary amino groups among all the primary to tertiary amino groups is 40% or more in terms of the number of groups. The more within these ranges, the easier the desorption can be achieved.
[0011] (A. Polyethyleneimine compound and B. Polyethyleneimine compound common to a mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent) The polyethyleneimine compound common to A and B preferably has an amine value of 10.0 mmol / g or more and 25.0 mmol / g or less. The polyethyleneimine compound common to A and B does not include C. siloxane-modified polyethyleneimine compound.
[0012] (B. Regarding the glycidyl group-containing silane coupling agent and / or the isocyanate group-containing silane coupling agent in the mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent) In this case, the polyethyleneimine compound may be one or more of the above-mentioned compounds. Examples of the silane coupling agent containing a glycidyl group include 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropylmethoxydimethoxysilane, 3-glycidyloxypropylmethoxydiethoxysilane, 3-glycidyloxypropyltriethoxysilane, etc. Examples of the silane coupling agent containing an isocyanate group include 3-isocyanatepropyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, 2-isocyanateethyltriethoxysilane, 2-isocyanateethyltrimethoxysilane, etc.
[0013] (C. Siloxane-modified polyethyleneimine compound) The siloxane-modified polyethyleneimine compound is a compound having the formula: RZ-SiY3 and a silane coupling agent-modified polyethyleneimine compound, i.e., a siloxane-modified polyethyleneimine compound, can be used which is obtained by reacting a silane coupling agent which is at least one amine-reactive hydrolyzable organosilane represented by the formula: [wherein R represents an amine-reactive group selected from the group consisting of an isocyanate group, an oxiranyl group, a glycidoxy group, an acryloxy group, a carbethoxy group, a carbomethoxy group, a vinylsulfonyl group, and an acrylamide group, Z represents a divalent organic group containing a carbon atom, and each Y independently represents a hydrolyzable group] with a component comprising This siloxane-modified polyethyleneimine compound has a structure in which the group R of the silane coupling agent reacts with the amino group of the polyethyleneimine, and the silane coupling agent is bonded to the polyethyleneimine. The amine value of the siloxane-modified polyethyleneimine compound is preferably 5.0 mmol / g or more and 15.0 mmol / g or less. It should be noted that C. siloxane-modified polyethyleneimine compound is not included in the above A. polyethyleneimine compound and B. polyethyleneimine compound, and is a compound different from the polyethyleneimine compound.
[0014] The coating amount of the polyethyleneimine compound on the printing substrate is 0.010 g / m 2 More preferably, 0.015 g / m2 or more is preferable, and 0.020 g / m2 or more is more preferable. 2 More preferably, the content is 0.400 g / m or more. 2 Less than 0.300 g / m is preferred. 2 Less than 0.200 g / m is more preferable. 2 More preferably, 0.100 g / m or less. 2 The following are most preferred: The detachment primer composition may or may not contain polyolefin resin particles, inorganic metal salts, or organic metal salts.
[0015] <Method for producing a release primer composition> The release primer composition (1) can be obtained by adding a solvent to a polyethyleneimine compound and stirring the mixture, and (2) can be obtained by adding a solvent to a polyethyleneimine compound and stirring the mixture, and then further adding a silane coupling agent containing a glycidyl group and / or a silane coupling agent containing an isocyanate group and stirring the mixture. (3) can be obtained by adding a solvent to siloxane-modified polyethyleneimine and stirring the mixture. The solvent can be a mixture of water and one or more alcohols such as methanol, ethanol, and isopropyl alcohol.
[0016] [Resin substrate] The resin substrate in the present invention may be a substrate made of a known resin on whose surface printing can be performed. Examples of such resin substrates include polyesters such as polyethylene terephthalate (PET), polyolefins such as polyethylene (PE) and polypropylene (PP), polyamides such as nylon, the above resin films having a metal layer such as aluminum, the above resin films having a transparent deposition layer, shrinkable polypropylene films (particularly shrinkable untreated polypropylene films), shrinkable polyvinyl chloride films, shrinkable polyethylene phthalate films, and other shrinkable plastic films. Furthermore, a laminate having a thermoplastic resin layer and an ethylene-based resin layer may or may not be used as the resin substrate. As such a resin substrate, there can be used a resin film that serves as a substrate for known lamination, a resin film for surface printing or shrink printing, a resin film laminated to a paper substrate, and the like, as described below. Furthermore, after forming a printing ink composition layer on a substrate via a detachable primer composition layer, the detachable primer composition of the present invention may be applied onto the printed layer to form a sealant layer by a dry lamination method or an extrusion lamination method.
[0017] [Print format] The detachment primer composition of the present invention is formed so as to be located between the surface of the resin substrate and the printed layer in a method of printing on a resin substrate. It is used in reverse printing, front printing, shrink printing, etc. In addition, in a printed matter in which the resin substrate, the detachment primer layer, and the printed layer are formed in this order, any known layer may be further formed between any of these layers or on the surface of the printed matter. When forming the resin substrate, the detachment primer layer, the adhesive layer, and the paper layer, any known layer may be further formed between any of these layers or on the surface of the obtained laminate. Also, in a method in which an adhesive is applied to a base film and a paper base is bonded to the base film to form a laminate paper, and printing is then performed on the paper base side of the laminate paper, the printing medium is formed between the base film and the adhesive layer. Hereinafter, the printing formats in which the detachment primer composition of the present invention can be used will be described in the order of reverse printing, front printing, shrink printing, and printing on the paper substrate side of laminated paper in which an adhesive is applied to a substrate film and a paper substrate is bonded thereto.
[0018] (Pigments) (Components that can be contained in common in reverse printing ink compositions, front printing ink compositions, and shrink printing ink compositions) In printing using the primer composition of the present invention, the printing ink composition may contain one or more pigments selected from inorganic and organic pigments that have been conventionally used. Examples of inorganic pigments include color pigments such as titanium oxide, red iron oxide, antimony red, cadmium yellow, cobalt blue, Prussian blue, ultramarine blue, carbon black, and graphite, and examples of extender pigments include silica particles, calcium carbonate, kaolin, clay, barium sulfate, aluminum hydroxide, and talc. Of these, it is preferable to use titanium oxide as a white pigment. Examples of the organic pigment include soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments. The content of these pigments in the printing ink composition is usually about 1 to 50 mass %. (A pigment used in an ink composition printed on the paper substrate side of laminated paper, which is made by applying an adhesive to a substrate film and bonding the substrate to the paper substrate.) As the pigment used in the ink composition to be printed on the paper substrate side, pigments that have been conventionally used in flexographic printing ink compositions can be used. Specifically, examples of inorganic pigments include colored pigments such as titanium oxide, red iron oxide, antimony red, cadmium yellow, cobalt blue, Prussian blue, ultramarine blue, carbon black, and graphite. Examples of organic pigments include soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments. The above pigments can be used alone or in combination of two or more. The concentration of the pigment in the flexographic printing ink composition is 5 to 60% by mass, typically 6 to 35% by mass for organic pigments and 30 to 60% by mass for inorganic pigments.
[0019] [Print layer] <<Reverse printing>> The reverse printing ink composition for forming the printed layer in the present invention contains, in addition to the above-mentioned pigment, a binder resin and various additives. <Binder resin> The binder resin includes a polyurethane resin, preferably a polyurethane resin having an amine value from the viewpoints of the stability, adhesiveness and lamination suitability of the printing ink composition.
[0020] (Polyurethane resin) The polyurethane resin may contain a polyurethane resin that is not modified with an acid and / or a polyurethane resin that is modified with an acid. The polyurethane resin that is not modified with an acid is a polyurethane resin that does not have acidic groups such as carboxylic acid groups, sulfonic acid groups, and phosphoric acid groups at the molecular terminals and / or other positions in the molecule. The polyurethane resin that is modified with an acid is a polyurethane resin that has acidic groups such as carboxylic acid groups, sulfonic acid groups, and phosphoric acid groups at the molecular terminals and / or other positions in the molecule. The printed layer can be smoothly detached from the resin substrate whether the printed layer is formed from an ink composition that uses an acid-modified polyurethane resin as a vehicle or an ink composition that uses a resin that is inherently difficult to detach, such as a non-acid-modified polyurethane resin, as a vehicle.
[0021] As such a polyurethane resin, a polyurethane resin that is generally used in printing ink compositions can be used. Among them, from the viewpoints of the stability over time, adhesion, and lamination suitability of the printing ink composition, polyurethane resins having amino groups (having an amine value) are preferred. Among polyurethane resins having amino groups, polyurethane resins having at least one selected from a primary amino group, a secondary amino group, and a tertiary amino group at the molecular end, particularly at least one selected from a primary amino group and a secondary amino group at the molecular end, are more preferred. More preferred is a polyurethane resin having a hydroxyl group and at least one type of amino group selected from a primary amino group, a secondary amino group and a tertiary amino group at the molecular terminal. The polyurethane resin has a specific functional group such as the amino group, and as a result, the reverse printing ink composition has excellent printability and adhesiveness. The amine value of the acid polyurethane resin is preferably 1.0 to 15.0 mgKOH / g, more preferably 2.0 to 8.0 mgKOH / g. If the amine value is less than 1.0 mgKOH / g, the adhesion of the printing ink composition for film of the present invention to the film may decrease, and further, the lamination suitability may decrease. If the amine value is more than 15.0 mgKOH / g, the blocking resistance may decrease. In the present invention, the amine value means the amine value per 1 g of solid content, and is measured by potentiometric titration (e.g., COMTITE (AUTOTITRA)) using a 0.1 N aqueous hydrochloric acid solution. This refers to the value measured using a TOR COM-900, BURET B-900, TITSTATION K-900, or Hiranuma Sangyo Co., Ltd.) and then converted into the equivalent amount of potassium hydroxide. In addition, the polyurethane resin preferably has hydroxyl groups within the molecule and at the molecular terminals from the viewpoint of resolubility.
[0022] (non-acid-modified polyurethane resin) As the polyurethane resin that is not acid-modified, a polyurethane polyurea resin and / or a polyurethane polyurea resin obtained by using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound is preferable. The polyurethane polyurea resin is prepared by chain extension and / or terminal termination of a urethane prepolymer obtained from an organic diisocyanate component and a polymer diol component. The polyurethane polyurea resin obtained by using the ketiminated compound is a polyurethane polyurea resin obtained by reacting a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound in an organic solvent with a urethane prepolymer as a chain extender and / or reaction terminator, or b. a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound in an organic solvent with a urethane prepolymer, stirring and mixing, adding water, and then carrying out chain extension and reaction termination to obtain a polyurethane polyurea resin. By using the above a and / or b, the amine odor of the reverse printing ink composition obtained is reduced and the stability over time is excellent. In consideration of the environmental aspect, the polyurethane polyurea resin may contain a biomass polyurethane polyurea resin.
[0023] (non-acid-modified polyurethane polyurea resin) The non-acid-modified polyurethane polyurea resin has at least one type selected from a primary amino group and a secondary amino group at the molecular terminal. More preferred is a non-acid-modified polyurethane polyurea resin which has a hydroxyl group and at least one type selected from a primary amino group and a secondary amino group at the molecular terminal. As these polyurethane polyurea resins, polyurethane resins obtained by synthesizing a urethane prepolymer by reacting an organic diisocyanate compound with a polymeric diol compound and reacting this with a chain extender and a reaction terminator described below can be suitably used.
[0024] (Synthesis of urethane prepolymer) Each of the above urethane prepolymers is obtained by reacting the following organic diisocyanate compound with a polymeric diol compound.
[0025] (Organic diisocyanate compounds) Examples of the organic diisocyanate compound include aromatic diisocyanate compounds such as tolylene diisocyanate, alicyclic diisocyanate compounds such as 1,4-cyclohexane diisocyanate, isophorone diisocyanate, and dicyclohexylmethane-4,4-diisocyanate (hydrogenated MDI), aliphatic diisocyanate compounds such as hexamethylene diisocyanate, and aromatic aliphatic diisocyanate compounds such as α,α,α',α'-tetramethylxylylene diisocyanate. These organic diisocyanate compounds can be used alone or in combination of two or more. Among them, alicyclic diisocyanate compounds, aliphatic diisocyanate compounds, and aromatic aliphatic diisocyanate compounds are more preferred.
[0026] In addition, as other organic diisocyanate compounds, aromatic diisocyanate compounds such as 1,3- and / or 1,4-phenylene diisocyanate, 4,4-diisocyanatobiphenyl, 3,3-dimethyl-4,4-diisocyanatobiphenyl, etc.; alicyclic diisocyanate compounds such as cyclohexylene diisocyanate, methylcyclohexylene diisocyanate (hydrogenated TDI), etc.; aliphatic diisocyanate compounds such as ethylene diisocyanate, tetramethylene diisocyanate, dodecamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, etc.; and aromatic aliphatic diisocyanate compounds such as m- and / or p-xylylene diisocyanate (XDI), etc. can also be used. When other organic diisocyanate compounds are used in combination, the number of isocyanate groups of the other organic diisocyanate compounds can be 50% or less, more preferably 30% or less, and even more preferably 10% or less, of the total number of isocyanate groups of all the organic diisocyanate compounds. Alternatively, the amount of other organic diisocyanate compounds is 50 parts by mass or less, more preferably 30 parts by mass or less, and further preferably 10 parts by mass or less, based on 100 parts by mass of all organic diisocyanate compounds.
[0027] (Polymer diol compound) Examples of the polymer diol compound include polyalkylene glycols such as polyethylene glycol and polypropylene glycol, polyether diol compounds such as alkylene oxide adducts of bisphenol A with ethylene oxide and propylene oxide, polyester diols obtained by condensation reaction of one or more dibasic acids such as adipic acid, sebacic acid, and phthalic anhydride with one or more glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, and 3-methyl-1,5-pentanediol, polyester diol compounds such as polycaprolactone diols, etc. These polymer diol compounds can be used alone or in combination of two or more. In addition to the above-mentioned polymeric diol compounds, one or more of alkanediols such as 1,4-pentanediol, 2,5-hexanediol, and 3-methyl-1,5-pentanediol, and low molecular weight diol compounds such as ethylene glycol, propylene glycol, 1,4-butanediol, and 1,3-butanediol can be used in combination.
[0028] The polymer diol compound preferably has a number average molecular weight of 1,000 to 8,000, more preferably 1,000 to 5,500, and even more preferably 1,000 to 4,000. Moreover, as the polymer diol compound, one containing 3-methyl-1,5-pentylene adipate diol can be selected. In this case, the following polymer diol compounds can be used in combination. Examples of polymeric diol compounds other than 3-methyl-1,5-pentylene adipate diol include polyester diols obtained by condensation reaction of one or more dibasic acids such as adipic acid, sebacic acid, phthalic anhydride, etc. with one or more glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, etc., polyester diol compounds such as polycaprolactone diols, and further, polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polyether diol compounds such as alkylene oxide adducts of bisphenol A with ethylene oxide, propylene oxide, etc. These polymeric diol compounds can be used alone or in combination of two or more.
[0029] Among the above, 3-methyl-1,5-pentylene adipate diol having a number average molecular weight of 1,000 to 8,000 obtained by a condensation reaction of adipic acid and 3-methyl-1,5-pentanediol is preferred, and 3-methyl-1,5-pentylene adipate diol having a number average molecular weight of 1,000 to 4,000 is more preferred. When other polymer diol compounds are used in combination, the number of hydroxyl groups of the other polymer diol compounds can be 70% or less, more preferably 55% or less, and even more preferably 40% or less, of the total number of hydroxyl groups of all the polymer diol compounds. Alternatively, the amount of the other polymer diol compounds is 50 parts by mass or less, more preferably 35 parts by mass or less, and further preferably 20 parts by mass or less, based on 100 parts by mass of the total polymer diol compounds. When the organic solvent of the printing ink composition for reverse printing is a mixed solvent system of an ester-based solvent and an alcohol-based solvent (hereinafter sometimes referred to as a "mixed liquid") described below, using a polyether diol compound, preferably polypropylene glycol, as the polymer diol compound tends to increase the solubility of the resulting polyurethane resin and also tends to improve printing suitability such as gradation reproduction and anti-fogging properties, which is preferable in that it enables the design of a wide range of printing ink compositions in accordance with the required performance.
[0030] (Non-acid-modified biomass polyurethane polyurea resin) The polyurethane resin may contain a biomass polyurethane polyurea resin that is not modified with an acid, taking into consideration the environmental aspect. The biomass polyurethane polyurea resin that is not modified with an acid will be described below. In the description of the biomass polyurethane polyurea resin that is not modified with an acid, the description common to the above-mentioned polyurethane polyurea resin that is not modified with an acid will be omitted as appropriate. The non-acid-modified biomass polyurethane polyurea resin is a polyurethane resin containing a biomass-derived (plant-derived) component. The non-acid-modified biomass polyurethane resin can contribute to preventing global warming and reducing the environmental load compared to the case of using other exhaustible resources. The non-acid-modified biomass polyurethane polyurea resin is preferably obtained by synthesizing a biomass urethane prepolymer by reacting a biopolyester polyol compound with an organic diisocyanate compound, and reacting this with a chain extender and a reaction terminator as necessary, and more preferably the isocyanate compound is a plant-derived bioisocyanate.
[0031] (Isocyanate compounds) In addition to the organic diisocyanate described in the above non-acid-modified polyurethane polyurea resin, a diisocyanate derived from vegetable oil can be used. The organic diisocyanate compound derived from vegetable oil can be obtained by converting a divalent carboxylic acid derived from a plant into a terminal amino group by acid amidation and reduction, and then reacting with phosgene to convert the amino group into an isocyanate group. Examples of bio-polyisocyanates derived from plants include dimer acid diisocyanate (DDI), octamethylene diisocyanate, and decamethylene diisocyanate. In addition, a plant-derived isocyanate compound can be obtained by using a plant-derived amino acid as a raw material and converting its amino group into an isocyanate group. For example, lysine diisocyanate (LDI) can be obtained by methyl esterifying the carboxyl group of lysine, and then converting the amino group into an isocyanate group. In addition, 1,5-pentamethylene diisocyanate can be obtained by decarbonating the carboxyl group of lysine, and then converting the amino group into an isocyanate group.
[0032] (Biopolyester polyol compound) The biopolyester polyol compound (biomass polyester polyol) will be described below. In consideration of the environmental aspect, among the biopolyester polyol compounds, a biopolyester polyol compound obtained by synthesis from a material containing a plant-derived component may be used in combination as the other polymer diol compound. In addition, a non-acid-modified polyurethane polyurea resin obtained by reacting a polyester polyol compound including a biopolyester polyol compound with the above-mentioned specific isocyanate compound can be mixed with the non-acid-modified polyurethane polyurea resin of the present invention and used. For this reason, the biopolyester polyol compound may be a biopolyester polyol obtained by reacting a short-chain diol compound having 2 to 4 carbon atoms with a carboxylic acid compound. It is more preferable that at least one of the short-chain diol compound and the carboxylic acid compound of the biopolyol component is derived from a plant, and it is even more preferable that both are derived from a plant. The plant-derived short-chain diol compound having 2 to 4 carbon atoms is not particularly limited. For example, the short-chain diol compound may be 1,3-propanediol, 1,4-butanediol, ethylene glycol, etc., which are obtained from plant raw materials by the following method. These may be used in combination. 1,3-propanediol can be produced from glycerol via 3-hydroxypropylaldehyde (HPA) by a fermentation method in which glucose is obtained by decomposing plant resources (such as corn, etc.). The 1,3-propanediol component produced by a biomethod such as the fermentation method is safer than the 1,3-propanediol component of the EO production method, and useful by-products such as lactic acid can be obtained, and the production cost can be kept low. 1,4-butanediol can be produced by producing glycol from plant resources, fermenting it to obtain succinic acid, and hydrogenating it. Ethylene glycol can also be produced from bioethanol obtained by a conventional method via ethylene.
[0033] The carboxylic acid compound derived from a plant is not particularly limited. For example, the carboxylic acid compound is sebacic acid, succinic acid, lactic acid, glutaric acid, dimer acid, etc. These may be used in combination. Among these, the carboxylic acid compound preferably contains at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid. In addition, 0.05 to 0.5 parts by mass of malic acid may be contained per 100 parts by mass of sebacic acid. The biopolyester polyol compound is produced as a 100% plant-derived biopolyester polyol by appropriately condensing a plant-derived short-chain diol compound and a plant-derived carboxylic acid. Specifically, polytrimethylene sebacate polyol is obtained by directly dehydrating and condensing plant-derived sebacic acid and plant-derived 1,3-propanediol. Also, polybutylene succinate polyol is obtained by directly dehydrating and condensing plant-derived succinic acid and plant-derived 1,4-butanediol. One or more of these biopolyester polyol compounds may be used. The urethane prepolymer obtained by using these plant-derived components may be contained in an amount of 10% by mass or more, or 40% by mass or more, calculated as solid content, of the total urethane prepolymer.
[0034] (Chain extenders and reaction terminators) Next, the chain extender and reaction terminator used in the non-acid-modified polyurethane polyurea resin and the non-acid-modified biomass polyurethane polyurea resin will be described. The chain extender may be any of the known chain extenders used in polyurethane polyurea resins as binders for printing ink compositions. Examples of the chain extender include, among polyamine compounds, aliphatic diamines such as ethylenediamine, propylenediamine, tetramethylenediamine, and hexamethylenediamine; alicyclic diamines such as isophoronediamine and 4,4'-dicyclohexylmethanediamine; aromatic diamines such as toluylenediamine; aromatic aliphatic diamines such as xylylenediamine; diamines having a hydroxyl group such as N-(2-hydroxyethyl)ethylenediamine (aminoethylethanolamine), N-(2-hydroxyethyl)propylenediamine, and N,N'-di(2-hydroxyethyl)ethylenediamine; and diol compounds such as ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, diethylene glycol, and triethylene glycol. Furthermore, polyamine compounds such as diethylenetriamine and triethylenetetramine can be used in combination within the range in which the polyurethane polyurea resin does not gel. Examples of reaction terminators that introduce primary and secondary amino groups to the ends of polyurethane polyurea resins include polyamine compounds such as aliphatic diamines such as ethylenediamine, propylenediamine, tetramethylenediamine, and hexamethylenediamine, alicyclic diamines such as isophoronediamine and 4,4'-dicyclohexylmethanediamine, polyamines such as diethylenetriamine and triethylenetetratriamine, aromatic diamines such as toluylenediamine, aromatic aliphatic diamines such as xylenediamine, and diamines having hydroxyl groups such as N-(2-hydroxyethyl)ethylenediamine (aminoethylethanolamine) and N-(2-hydroxyethyl)propylenediamine. Among these, polyamines having primary amino groups such as diethylenetriamine and triethylenetetratriamine are preferred. Examples of reaction terminators that introduce hydroxyl groups into polyurethane polyurea resins include alkanolamines such as monoethanolamine and diethanolamine, and diamines having hydroxyl groups such as N-(2-hydroxyethyl)ethylenediamine and N-(2-hydroxyethyl)propylenediamine. Known reaction terminators such as monoamine compounds and monoalcohol compounds can also be used, and specific examples include monoalkylamines such as n-propylamine and n-butylamine, dialkylamines such as di-n-butylamine, and monoalcohols such as ethanol.
[0035] As a method for producing the above-mentioned non-acid-modified polyurethane polyurea resin and non-acid-modified biomass polyurethane polyurea resin, a known method for producing a polyurethane resin can be used as is using the above-mentioned materials. In addition, since the hardness of the obtained polyurethane resin varies depending on the mass average molecular weight, chemical structure, and equivalent ratio of each component, it is possible to adjust the printability and lamination suitability by appropriately combining these components. The mass average molecular weight of the non-acid-modified polyurethane polyurea resin and the non-acid-modified biomass polyurethane polyurea resin is preferably 10,000 to 70,000, and more preferably 20,000 to 60,000. Furthermore, in order to provide appropriate flexibility and increase laminate strength, a polyurethane resin having no urea bond and a mass average molecular weight of 1,000 to 70,000 can be blended as the polyurethane resin.
[0036] (Reaction of organic diisocyanate compound with polymeric diol compound) In addition, the use ratio of the organic diisocyanate compound and the polymer diol compound when reacting them is usually in the range of 1.2:1.0 to 3.0:1, more preferably 1.3:1.0 to 2.0:1, in terms of the equivalent ratio (isocyanate index) of isocyanate group:hydroxyl group. If the isocyanate index is smaller than 1.2, the resulting polyurethane polyurea resin is likely to be a soft non-acid-modified polyurethane polyurea resin or a non-acid-modified biomass polyurethane polyurea resin, and the blocking resistance may be low when the printing ink composition is printed. In this case, it may be necessary to use the resin in combination with another hard resin.
[0037] A catalyst can be used in the reaction of an organic diisocyanate compound with a polymer diol compound to obtain the non-acid-modified polyurethane polyurea resin and the non-acid-modified biomass polyurethane polyurea resin used in the present invention. Among these, it is preferable to use an organometallic compound. Examples of such an organometallic compound include titanium compounds such as dibutyltitanium dichloride, tetrabutyltitanium, and butoxytitanium trichloride, dibutyltin sulfide, tributyltin sulfide, tributyltin oxide, dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin dimaleate, dibutyltin dilaurate, dibutyltin diacetate, dioctyltin dilaurate, tributyltin dilaurate, and the like. Examples of suitable compounds include tin compounds such as tin acetate, tributyltin chloride, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, tributyltin trichloroacetate, and tin 2-ethylhexanoate, lead compounds such as lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate, and further compounds such as iron 2-ethylhexanoate, iron acetylacetonate, cobalt benzoate, cobalt 2-ethylhexanoate, zinc naphthenate, zinc 2-ethylhexanoate, and zirconium naphthenate. Among these, titanium compounds such as tetrabutyl titanate are preferred. Also, tertiary amine compounds can be used, such as triethylamine, triethylenediamine, 1,4-diazabicyclo(2,2,2)octane, and 1,8-diazabicyclo(5,4,0)-undecene-7 (DBU).
[0038] (Polyurethane polyurea resin not modified with acid obtained by using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound, and biomass polyurethane polyurea resin not modified with acid obtained by using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound) The non-acid-modified polyurethane polyurea resin obtained by using a compound in which the amino group of a polyamine compound has been ketiminated with a ketone compound, and the non-acid-modified biomass polyurethane polyurea resin obtained by using a compound in which the amino group of a polyamine compound has been ketiminated with a ketone compound can be produced by using a ketimine compound obtained by previously ketiminizing a polyamine compound with an excess amount of a ketone compound among the above chain extenders and / or reaction terminators, c. employing a compound in which the amino group of a polyamine compound has been ketiminized with a ketone compound in an organic solvent and reacting it with a urethane prepolymer and / or a biomass urethane prepolymer, or d. employing a compound in which the amino group of a polyamine compound has been ketiminized with a ketone compound in an organic solvent and adding it to the urethane prepolymer and / or biomass urethane prepolymer and stirring and mixing, further adding water, and then carrying out chain extension and reaction termination. In particular, it is preferable to employ one or more selected from the above chain extenders and reaction terminators: isophoronediamine, N-(2-hydroxyethyl)ethylenediamine, and ethylenediamine. The polyamine compound ketiminated with a ketone compound has a structure in which the oxygen atom of the ketone compound is substituted with the nitrogen atom of the amino group of the polyamine compound. The ketone compound to be used is preferably acetone, diethyl ketone, methyl ethyl ketone, diacetone alcohol, or methyl isobutyl ketone. In this ketiminization reaction, it is preferable not to use any solvent other than the ketone compound. However, as a solvent other than the ketone compound, an alcohol compound can be used, and among them, isopropyl alcohol can be used. The absence of a solvent other than the ketone compound is defined as ketiminization under solvent-free conditions. Note that a polar organic solvent may be added instead of solvent-free conditions, as long as it does not inhibit the subsequent chain extension reaction or the fact that the non-acid-modified polyurethane polyurea resin and the non-acid-modified biomass polyurethane polyurea resin have no odor. The present invention may be a printing ink composition containing a non-acid-modified polyurethane polyurea resin and / or a non-acid-modified biomass polyurethane polyurea resin obtained by a process of chain extension or reaction termination using a ketiminated chain extender and / or a reaction terminator by the above method c or d, and the printing ink composition and printed matter printed therewith do not emit a ketimine odor.In addition, the printing ink composition has an effect of increasing the peel strength when laminated to the printed surface by means of dry lamination, extrusion lamination, or the like. The ketiminated amines and the like may be used as a chain extender, a reaction terminator, or both a chain extender and a reaction terminator.
[0039] <Synthesis of non-acid-modified polyurethane polyurea resin obtained by using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound, and non-acid-modified biomass polyurethane polyurea resin obtained by using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound> A ketimine compound obtained by previously ketiminizing a polyamine compound with an excess amount of a ketone compound is used for a urethane prepolymer and / or a biomass urethane prepolymer obtained by reacting an organic diisocyanate compound with a polymer diol compound, e. employing a compound in which the amino group of a polyamine compound has been ketiminized with a ketone compound in an organic solvent and reacting it with the urethane prepolymer and / or biomass urethane prepolymer, or f. employing a compound in which the amino group of a polyamine compound has been ketiminized with a ketone compound in an organic solvent, adding it to the urethane prepolymer and / or biomass urethane prepolymer and stirring and mixing, further adding water, and then carrying out chain extension and reaction termination, thereby enabling to obtain a non-acid-modified polyurethane polyurea resin and a non-acid-modified biomass polyurethane polyurea resin obtained using a compound in which the amino group of a polyamine compound has been ketiminized with a ketone compound. When a solvent is used in the reaction, an ester-based solvent and / or an alcohol-based solvent is preferable, a mixture of an ester-based solvent and an alcohol-based solvent is more preferable, propyl acetate and isopropyl alcohol are further preferable, and a mass ratio of propyl acetate:isopropyl alcohol in the range of 1:1 to 5:1 is most preferable.
[0040] (Acid-modified polyurethane resin, acid-modified biomass polyurethane resin) As the polyurethane resin in the present invention, an acid-modified polyurethane resin and / or an acid-modified biomass polyurethane resin can also be used. It may be used together with the above-mentioned non-acid-modified polyurethane resin and / or non-acid-modified biomass polyurethane resin, or only the acid-modified polyurethane resin and / or the acid-modified biomass polyurethane resin, or only the non-acid-modified polyurethane resin and / or non-acid-modified biomass polyurethane resin may be used. The acid-modified polyurethane resin and the acid-modified biomass polyurethane resin can be obtained by reacting the polymer diol component with a tetrabasic acid anhydride such as pyromellitic anhydride as the polymer diol compound constituting the polyurethane resin, or by using a polymer diol compound having a free carboxyl group obtained by ring-opening polymerization of lactones using dimethylolpropionic acid, dimethylolbutanoic acid, or the like as an initiator, or by using a hydroxycarboxylic acid such as dimethylolpropionic acid or dimethylolbutanoic acid together with the polymer diol compound constituting the polyurethane resin. The acid value of the acid-modified polyurethane resin and the acid-modified biomass polyurethane resin is preferably 70 mgKOH / g or less.
[0041] (Vinyl chloride / vinyl acetate copolymer) The vinyl chloride-vinyl acetate copolymer that may be incorporated in the reverse printing ink composition may be one produced by a known method using the vinyl chloride monomer and vinyl acetate monomer conventionally used in gravure printing ink compositions as essential components, with fatty acid vinyl monomers such as vinyl propionate, vinyl monochloroacetate, vinyl versatate, vinyl laurate, vinyl stearate, vinyl benzoate, and monomers having functional groups such as hydroxyl groups as copolymerization components, as necessary. Vinyl chloride-vinyl acetate copolymers having hydroxyl groups can be obtained by partially saponifying the acetate moieties and by introducing (meth)acrylic monomers having hydroxyl groups. In the case of vinyl chloride-vinyl acetate copolymers having hydroxyl groups obtained by partially saponifying the acetate ester moieties, the film properties and dissolution behavior of the resin are determined by the ratio of the structural units based on the reactive sites of vinyl chloride (formula 1 below), the structural units based on the reactive sites of vinyl acetate (formula 2 below), and the structural units based on the saponification of the reactive sites of vinyl acetate (formula 3 below) in the molecule. That is, the structural units based on the reactive sites of vinyl chloride impart strength and hardness to the resin film, the structural units based on the reactive sites of vinyl acetate impart adhesion and flexibility, and the structural units based on the saponification of the reactive sites of vinyl acetate impart good solubility in the organic solvent system of the environmentally friendly printing ink composition. Formula 1 -CH2-CHCl- Formula 2 -CH2-CH(OCOCH3)- Formula 3 -CH2-CH(OH)-
[0042] From the viewpoint of solubility in organic solvents described below and printability used in the reverse printing ink composition, the vinyl chloride-vinyl acetate copolymer may have various functional groups in the molecule. When an environmentally friendly solvent is used as the organic solvent, the vinyl chloride-vinyl acetate copolymer preferably has a hydroxyl group concentration of 50 to 200 mg KOH / g. Commercially available products of such vinyl chloride-vinyl acetate copolymers include, for example, Solbin A, AL, TA5R, TA2, TA3, TAO, and TAOL.
[0043] (Vinyl chloride-acrylic copolymer) The vinyl chloride-acrylic copolymer that can be incorporated in the reverse printing ink composition is a copolymer of vinyl chloride and an acrylic monomer as the main component, and the form of the copolymer is not particularly limited. For example, the acrylic monomer may be incorporated in the main chain of polyvinyl chloride in a block or random manner, or may be graft-copolymerized in the side chain of polyvinyl chloride.
[0044] The acrylic monomer may be a (meth)acrylic acid ester, an acrylic monomer having a hydroxyl group, etc. Examples of the (meth)acrylic acid ester include a (meth)acrylic acid alkyl ester, and the alkyl group may be linear, branched, or cyclic, but is preferably a linear alkyl group. For example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, and the like.
[0045] Examples of acrylic monomers having a hydroxyl group include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; glycol mono(meth)acrylates such as polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and 1,4-cyclohexanedimethanol mono(meth)acrylate; caprolactone-modified (meth)acrylate; and hydroxyethylacrylamide. The acrylic monomer may also have a functional group other than a hydroxyl group, such as a carboxyl group, an amide bond, an amino group, or an alkylene oxide group. The vinyl chloride-acrylic copolymer preferably has a mass average molecular weight of 10,000 to 70,000. From the standpoint of solubility in environmentally friendly organic solvents and adhesion to substrates, it is preferable that the vinyl chloride-acrylic copolymer has hydroxyl groups in an amount of 50 to 200 mg KOH / g.
[0046] The reverse printing ink composition may contain a polyurethane resin and (vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer) in a mass ratio of polyurethane resin / (vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer)=95 / 5 to 45 / 55, and preferably 92 / 8 to 70 / 30. In addition, the ratio of polyurethane resin / (vinyl chloride-vinyl acetate copolymer) may be in the range of 90 / 10 to 75 / 25, and the ratio of polyurethane resin / (vinyl chloride-acrylic copolymer) may be in the range of 95 / 5 to 85 / 15. By containing the polyurethane resin and the vinyl chloride-vinyl acetate copolymer and / or the vinyl chloride-acrylic copolymer in a ratio of 95 / 5 to 45 / 55, the reverse printing ink composition has better printability and adhesion to the film, and further has better lamination suitability when lamination processing is performed. If the ratio of the polyurethane resin to (vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer) exceeds 95 / 5, the proportion of (vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer) may become small, and adhesion to the film may become insufficient. On the other hand, if the polyurethane resin / (vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer) ratio is less than 45 / 55, the proportion of (vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer) will be high, and the printed matter formed using the printing ink composition will become hard, which may also result in insufficient adhesion to the film.
[0047] The combined content of the polyurethane resin and the vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer in the reverse printing ink composition is preferably 5 to 30% by mass. The reverse printing ink composition may contain one or more selected from an adhesion improver and an antiblocking agent, provided that the intended performance of the present invention is not impaired. It is preferable to use an adhesion improver and an antiblocking agent in combination.
[0048] (Adhesion improver) Examples of adhesion improvers that can be incorporated in the reverse printing ink composition include rosin and its derivatives, chlorinated polypropylene, dammar resin, etc., and it is desirable to contain at least one type, more preferably two or more types, selected from rosin and its derivatives.
[0049] (Rosin and its derivatives) Examples of rosin include gum rosin, tall oil rosin, wood rosin, etc. Generally, rosin is an amber-colored, amorphous resin obtained from pine trees, and since it is obtained naturally, it is a mixture, but it may be used after being isolated into its constituent components, namely abietic acid, neoabietic acid, palustric acid, pimaric acid, isopimaric acid, sandaracopimaric acid, and dehydroabietic acid, and these are also defined as rosin in the present invention. The rosin derivatives are compounds obtained by modifying the above-mentioned rosins, and specific examples thereof are listed below. (1) Hydrogenated rosin: A rosin whose weather resistance has been improved by adding hydrogen to the conjugated double bonds (hydrogenation). (2) Disproportionated rosin: Disproportionation is a process in which two molecules of rosin react with each other, and two molecules of abietic acid with conjugated double bonds are modified, one to an aromatic compound and the other to a molecule with a single double bond. In general, disproportionated rosin is less weather resistant than hydrogenated rosin, but its weather resistance is better than that of untreated rosin. (3) Rosin-modified phenolic resin: Rosin-modified phenolic resin is sometimes used as the main binder. Rosin-modified phenolic resin can be obtained by a known manufacturing method. (4) Rosin ester: An ester resin derived from rosin, which has long been used as a tackifier in adhesives and adhesives. (5) Rosin-modified maleic acid resin: This is obtained by adding maleic anhydride to rosin, and may also include those in which a hydroxyl-containing compound such as glycerin is esterified with the anhydride group and grafted, if necessary. (6) Polymerized rosin: A derivative containing dimerized resin acid derived from the natural resin rosin. In addition, known rosins and rosin derivatives can also be used, and these can be used alone or in combination. Furthermore, the acid value of the rosin and its rosin derivatives is preferably 120 mgKOH / g or more. When the acid value is 120 mgKOH / g or more, the laminate strength is improved. The acid value is more preferably 160 mgKOH / g or more. Furthermore, the total amount of the rosin and its derivatives used when blending is preferably 0.1 to 3.0 mass% in terms of solid mass% of the reverse printing ink composition.
[0050] (chlorinated polypropylene) The chlorinated polypropylene may have a chlorination degree of 20 to 50. A chlorinated polypropylene having a chlorination degree of less than 20 tends to have a decreased compatibility with organic solvents. On the other hand, when the chlorination degree exceeds 50, the chlorinated polypropylene tends to have a decreased adhesiveness to films. In the present invention, the chlorination degree is defined as the mass% of chlorine atoms in the chlorinated polypropylene resin. The chlorinated polypropylene is preferably a modified or unmodified chlorinated polypropylene having a mass average molecular weight of 5,000 to 200,000. When the mass average molecular weight is less than 5,000, the chlorinated polypropylene tends to have a decreased adhesiveness. On the other hand, when the mass average molecular weight exceeds 200,000, the chlorinated polypropylene tends to have a decreased solubility in organic solvents. The amount of the chlorinated polypropylene to be used when blending is preferably 0.1 to 3.0 mass% in terms of solid mass% of the reverse printing ink composition.
[0051] (Dammar resin) Dammar resin, also written as damar or dammar, is a type of natural resin derived from plants. More specifically, it is a type of natural resin obtained from Dipterocarpaceae or Burseraceae plants that grow in Southeast Asia, such as Malaysia and Indonesia. When used, it is dissolved in an appropriate organic solvent to make a varnish. Since dammar resin does not contain chlorine, it is possible to eliminate or reduce chlorine compared to the use of chlorinated polypropylene in the printing ink composition. In addition, the amount of dammar resin used when blending it is preferably 3.0 mass% or less in terms of solid mass% of the printing ink composition for reverse printing.
[0052] (Anti-blocking agent) Examples of anti-blocking agents include silica particles, polyethylene wax, fatty acid amides, cellulose acetate butyrate resin, cellulose acetate propionate resin, soluble nitrocellulose, etc. It is preferable to contain one or more, preferably two or more, of silica particles, polyethylene wax, and fatty acid amides, and depending on the type of pigment, it is preferable to further contain cellulose acetate butyrate resin, cellulose acetate propionate resin, and soluble nitrocellulose.
[0053] <Silica particles> Examples of silica particles include natural products, synthetic products, crystalline, non-crystalline, hydrophobic, and hydrophilic particles. The silica particles preferably have an average particle size of 1.0 to 5.0 μm (the average particle size of silica particles means the particle size at 50% cumulative value (D50) in particle size distribution, and can be determined by the Coulter counter method). The silica particles may be hydrophilic silica having a hydrophilic functional group on the surface, or may be hydrophobic silica in which the hydrophilic functional group is modified with alkylsilane or the like to be hydrophobic. However, hydrophilic silica is preferable, and a printing ink composition containing hydrophilic silica particles has an effect of promoting the wetting and spreading of the printing ink composition during overprinting, and improving the overprinting effect (hereinafter sometimes referred to as "trapping property"). The amount of silica particles used is preferably 0.0 to 3.0% by mass, more preferably 0.1 to 1.0% by mass in the printing ink composition for reverse printing.
[0054] (Polyethylene wax) It is preferable to use a polyethylene wax having an average particle size in the range of 1.0 to 3.0 μm (the average particle size means the particle size measured by Honeywell Microtrac UPA). If the particle size of the polyethylene wax is smaller than 1.0 μm, the slipperiness and blocking properties may decrease, and if the particle size is larger than 3.0 μm, the trapping properties may decrease. The content of the polyethylene wax in the printing ink composition for reverse printing is preferably in the range of 0.1 to 1.5% by mass. If the content is less than 0.1% by mass, the desired effect cannot be obtained, and if the content is more than 1.5% by mass, the gloss may decrease.
[0055] (nitrocellulose) As the soluble nitrocellulose, soluble nitrocellulose that has been used in gravure printing ink compositions can be used. The soluble nitrocellulose is obtained by reacting natural cellulose with nitric acid to replace three hydroxyl groups in a six-membered ring of anhydrous glucopyranose group in natural cellulose with nitric acid groups to obtain a nitric acid ester. As the soluble nitrocellulose used in the present invention, one having a nitrogen content of 10 to 13% and an average degree of polymerization of 35 to 90 is preferably used. Specific examples include SS1 / 2, SS1 / 4, SS1 / 8, TR1 / 16, and NCRS-2 (KOREACNC LTD). The amount of soluble nitrocellulose used in the reverse printing ink composition is preferably in the range of 0.1 to 2.0% by mass depending on the type of pigment.
[0056] (Cellulose acetate propionate resin) As the cellulose acetate propionate resin, resins that have been conventionally used in gravure printing ink compositions can be used. Cellulose acetate propionate resin is obtained by triesterifying cellulose with acetic acid and propionic acid, followed by hydrolysis. Generally, resins with 0.6 to 2.5% by weight of acetylation, 42 to 46% by weight of propionylation, and 1.8 to 5% by weight of hydroxyl groups are commercially available. The cellulose acetate propionate resin is preferably used in the range of 0.1 to 3.0% by weight in the reverse printing ink composition, depending on the type of pigment.
[0057] (Cellulose acetate butyrate resin) As the cellulose acetate butyrate resin, resins that have been conventionally used in gravure printing ink compositions can be used. Cellulose acetate butyrate resin is obtained by triesterifying cellulose with acetic acid and butyric acid, followed by hydrolysis. Generally, resins with 2 to 30% by mass of acetylation, 17 to 53% by mass of butyrylation, and 1 to 5% by mass of hydroxyl groups are commercially available. The amount of cellulose acetate butyrate resin used in the reverse printing ink composition is preferably within the range of 0.1 to 3.0% by mass, depending on the type of pigment.
[0058] (Fatty acid amide) The fatty acid amide is not particularly limited as long as it has an amide group and a residue obtained by removing an acid group from a fatty acid. Examples of the fatty acid amide include monoamide, substituted amide, bisamide, methylol amide, and ester amide, and at least one selected from the group consisting of monoamide, substituted amide, and bisamide is preferable because it improves blocking resistance. The amount of the fatty acid amide used is preferably in the range of 0.01 to 1.0 mass% in the reverse printing ink composition.
[0059] Monoamides: Monoamides are represented by the following general formula (1): General formula (1) R1-CONH2 (In the formula, R1 represents a residue obtained by removing COOH from a fatty acid.) Specific examples of monoamides include lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, oleic acid amide, and erucic acid amide.
[0060] Substituted amide: The substituted amide is represented by the following general formula (2): General formula (2) R2-CONH-R3 (In the formula, R2 and R3 represent a residue obtained by removing COOH from a fatty acid, and may be the same or different.) Specific examples of the substituted amide include N-oleyl palmitic acid amide, N-stearyl stearic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, and N-stearyl erucic acid amide.
[0061] Bisamides: Bisamides are represented by the following general formula (3) or (4). General formula (3) R4-CONH-R5-HNCO-R6 General formula (4) R7-NHCO-R8-CONH-R9 (In the formula, R4, R6, R7, and R9 represent a residue obtained by removing COOH from a fatty acid and may be the same or different, and R5 and R8 represent an alkylene group or arylene group having 1 to 10 carbon atoms.) Specific examples of bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-distearyl adipamide, N,N'-distearyl sebacic acid amide, N,N'-dioleyl adipamide, and N,N'-dioleyl sebacic acid amide.
[0062] Methylolamide: Methylolamide is represented by the following general formula (5). General formula (5) R10-CONHCH2OH (In the formula, R10 represents a residue obtained by removing COOH from a fatty acid.) Specific examples of methylol amides include methylol palmitic acid amide, methylol stearic acid amide, methylol behenic acid amide, methylol hydroxystearic acid amide, methylol oleic acid amide, and methylol erucic acid amide.
[0063] Ester amide: Ester amide is represented by the following general formula (6): General formula (6) R11-CONH-R12-OCO-R13 (In the formula, R11 and R13 represent a residue obtained by removing COOH from a fatty acid and may be the same or different, and R12 represents an alkylene group or arylene group having 1 to 10 carbon atoms.) Specific examples of ester amides include stearylamide ethyl stearate, oleylamide ethyl stearate, and the like. The melting point of the fatty acid amide is preferably 50 to 150°C. Moreover, the fatty acid constituting the fatty acid amide is preferably a saturated fatty acid having 12 to 22 carbon atoms and / or an unsaturated fatty acid having 16 to 25 carbon atoms, and more preferably a saturated fatty acid having 16 to 18 carbon atoms and / or an unsaturated fatty acid having 18 to 22 carbon atoms. Particularly preferred saturated fatty acids are lauric acid, palmitic acid, stearic acid, behenic acid, and hydroxystearic acid, and particularly preferred unsaturated fatty acids are oleic acid and erucic acid.
[0064] (Organic solvent) The printing ink composition for reverse printing, which forms a printing layer, is oil-based. The organic solvents used are the same as those of the ink compositions for front printing and shrink printing, and include, for example, alcohol-based solvents such as methanol, ethanol, isopropanol, normal propanol, butanol, isobutanol, and tert-butanol, aromatic hydrocarbon-based solvents such as toluene and xylene, aliphatic hydrocarbon-based solvents such as hexane, cyclohexane, methylcyclohexane, and ethylcyclohexane, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, ester-based solvents such as ethyl acetate, n-propyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, sec-butyl acetate, and tert-butyl acetate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol dimethyl Examples of the esters include glycol solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether, and esters thereof, and as the esters, acetates are mainly selected, such as ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate. These can be used alone or in combination of two or more. From the standpoint of environmental issues, it is preferable to use a mixed solvent of an ester-based organic solvent, an alcohol-based organic solvent and a ketone-based organic solvent, or a mixed solvent of an ester-based organic solvent and an alcohol-based organic solvent which is more environmentally friendly. Furthermore, the printing ink composition for reverse printing may contain 0.1 to 20 mass% of a glycol ether-based organic solvent in 100 mass% of the organic solvent in order to improve wetting and spreading properties. Specific examples of glycol ether-based organic solvents include ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, ethylene glycol mono n-propyl ether, ethylene glycol monoisopropyl ether, diethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, ethylene glycol monoisobutyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, propylene glycol mono n-propyl ether, diethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol diethyl ether, and the like.
[0065] It is preferable that the reverse printing ink composition contains water in order to reduce printing defects caused by static electricity, prevent plate fogging, and improve cell reproducibility. The amount of water used is preferably 10% by mass or less, more preferably 0.1 to 5.0% by mass, in the reverse printing ink composition.
[0066] (Other materials) The reverse printing ink composition may further contain various additives such as a pigment dispersant, an antistatic agent, a plasticizer, etc. A known method can be used to produce a printing ink composition using the above-mentioned constituent materials. Specifically, for example, a mixture of a binder resin, an organic solvent, and, if necessary, a pigment dispersant, etc., is milled using a high-speed mixer, a ball mill, a sand mill, an attritor, etc., and the remaining materials such as a thiocyanate and predetermined additives are further added and mixed to obtain the composition. Furthermore, a metal tetraalkoxide and / or a hydroxy acid may or may not be contained.
[0067] (Method for producing reverse printing ink composition) A method for producing a printing ink composition for reverse printing using these materials includes first stirring and mixing the pigment, binder resin, organic solvent, and, if necessary, pigment dispersant, surfactant, etc., and then grinding using various grinding machines, such as a bead mill, ball mill, sand mill, attritor, roll mill, pearl mill, etc., and further adding and mixing the fatty acid amide, chelating crosslinker, and remaining materials.
[0068] (Printing method using reverse printing ink composition and laminate obtained thereby) Next, a method for obtaining a laminate print using the reverse printing ink composition will be described. The reverse printing ink composition can also be used for purposes other than lamination. Methods for obtaining laminated prints include at least the following printing methods. For example, the release primer composition of the present invention is applied to a resin film that is a known substrate for lamination as a resin substrate. Then, a gravure printing ink composition for lamination is printed one or more times by gravure printing in-line or off-line. Next, another gravure lamination printing ink composition is printed by gravure printing at any position on the surface side of the printing ink layer for gravure lamination formed by these printings (the lower layer side from the surface layer after final lamination), and dried by a dryer. A resin film or the like can be laminated by various methods on the layer of the gravure laminate printing ink composition of the printed matter obtained by the above method to form a sealant layer, thereby obtaining a laminated printed matter for packaging bags, etc. Examples of the lamination method that can be used include an extrusion lamination method in which a molten polymer is laminated on the surface of the printed matter, with or without coating an anchor coating agent, and a dry lamination method in which an adhesive is applied to the surface of the printed matter and then a film-like polymer is laminated. The resin layer or film-like polymer formed by extrusion lamination can be a resin such as unstretched polypropylene or VMCPP (aluminum-deposited unstretched polypropylene). In particular, in the latter case, the sealant layer, VMCPP itself, can be removed in the removal step using the removal liquid described below.
[0069] The extrusion lamination method is a method of laminating a molten polymer by a known extrusion laminator, after coating, as necessary, an anchor coating agent such as a titanium-based, urethane-based, imine-based, polybutadiene-based agent on the surface of a printed material containing a layer of a printing ink composition, or without coating, and further, the molten resin can be laminated in a sandwich shape with other materials as an intermediate layer. In this case, it is not necessary to use a polyethyleneimine-based anchor coating agent. The molten polymer used in the extrusion lamination method may be a resin that has been used conventionally, such as low-density polyethylene, ethylene-vinyl acetate copolymer, polypropylene, etc. Among these, the effect of the present invention is enhanced when it is composed of low-density polyethylene, which is prone to generate carbonyl groups due to oxidation during melting.
[0070] The dry lamination method is a method in which a urethane-based, isocyanate-based, or other adhesive is applied to the surface of the layer made of the gravure laminate printing ink composition, and then a resin film is laminated using a known dry laminating machine. In particular, to obtain a packaging material for retort applications, aluminum foil can be sandwiched between the substrate and the resin film to be laminated. Such laminated products can also be used for boiling and retort applications after being made into bags and filled with the contents. Examples of the resin film used in this case include oriented and unoriented polyolefins such as polyethylene and polypropylene, polyester, nylon, cellophane, vinylon, etc. Furthermore, with regard to these resin films, films obtained by processing in advance such as coating or kneading an anti-fogging agent, or surface coating or kneading a matting agent can also be used. Furthermore, as the resin film, a film in which a barrier layer formed by depositing metal or coating a barrier resin on various printing plastic films can be used.
[0071] <<Surface printing>> The surface printing ink composition contains the above-mentioned pigment, a binder resin and various additives. <Binder Resin> The binder resin contained in the surface printing ink composition can be selected from the following resins, for example, a combination of cellulose resin and polyamide resin, a combination of cellulose resin and polyurethane resin, a combination of polyurethane resin and the above-mentioned vinyl chloride-vinyl acetate copolymer, a combination of acrylic resin and polyurethane resin, a combination of cellulose resin and acrylic resin, cellulose resin only, or the above-mentioned vinyl chloride-vinyl acetate copolymer only.
[0072] (Cellulosic resin) The cellulose resin may be any cellulose resin that has been used in conventional gravure printing ink compositions. Examples of such cellulose resins include nitrocellulose (nitro group-substituted), lower acyl group-substituted cellulose resins such as cellulose acetate, cellulose acetate propionate, and cellulose acetate butyrate (CAB), and lower alkyl group-substituted cellulose resins such as methyl cellulose and ethyl cellulose. The mass average molecular weight and degree of substitution of hydroxyl groups of these cellulose resins may be within the ranges used in ordinary printing ink compositions and paints, and may be used without any problems in the present invention.
[0073] The degree of substitution of hydroxyl groups is preferably about 1.3 to 2.7. In addition, from the viewpoint of heat resistance, the use of nitro group-substituted products is advantageous, and from the viewpoint of adhesion, lower acyl group-substituted products and lower alkyl group-substituted products are advantageous, so it is preferable to select and use them appropriately depending on the purpose. When a cellulose-based resin is contained, the content ratio of the polyurethane resin to the cellulose-based resin is preferably, in terms of mass, polyurethane resin:cellulose resin = 5:95 to 95:5. The content ratio of the polyamide resin to the cellulose-based resin is preferably, polyamide resin:cellulose resin = 95:5 to 70:30. The content ratio of the acrylic resin to the cellulose-based resin is preferably, acrylic resin:cellulose resin = 95:5 to 30:70.
[0074] (Polyurethane resin) As the polyurethane resin, a polyurethane resin obtained by reacting a polyisocyanate compound, a diol compound, and, if necessary, a chain extender, a reaction terminator, etc. can be used. Examples of the polyisocyanate compound that can be used herein include aliphatic diisocyanate compounds such as hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate; alicyclic diisocyanate compounds such as isophorone diisocyanate, hydrogenated xylylene diisocyanate and 4,4-cyclohexylmethane diisocyanate; aromatic aliphatic diisocyanate compounds such as xylylene diisocyanate and α,α,α',α'-tetramethylxylylene diisocyanate; and aromatic diisocyanate compounds such as toluylene diisocyanate and diphenylmethane diisocyanate. Furthermore, together with such a polyurethane resin, a known binder resin for gravure printing can be used.
[0075] Next, the diol compound is preferably a polymeric diol compound, and has a number average molecular weight of preferably more than 500 and not more than 3,000, more preferably 500 to 2,000, and may be composed of one kind of diol compound or may be a combination of a plurality of diol compounds. When the number average molecular weight of the diol compound is 500 or less, the adhesiveness tends to decrease, while when the number average molecular weight exceeds 3,000, the oil resistance tends to decrease. Specific examples of the diol compound include alkylene glycol compounds having a number average molecular weight of 100 or more, polyalkylene glycol compounds such as polyethylene glycol and polypropylene glycol, and polyether diol compounds obtained by polyaddition of oxyalkylenes such as ethylene oxide and propylene oxide, tetrahydrofuran, or the like to diol compounds such as low-molecular-weight alkylene glycols and bisphenols. Further examples include polyester diol compounds obtained by polycondensation of low molecular weight diol compounds such as linear glycols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol, branched glycols such as 1,2-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, and ethylbutylpropanediol, and ether-based diols such as diethylene glycol and triethylene glycol, and dicarboxylic acid compounds such as saturated and unsaturated aliphatic dicarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and maleic acid, and aromatic dicarboxylic acids such as phthalic acid, and polyester diol compounds obtained by ring-opening reaction of cyclic ester compounds such as lactones.
[0076] Furthermore, linear or side chain polycarbonate compounds, polybutadiene glycol compounds, etc. can also be used in combination. In addition, in consideration of the environment, it is preferable to use a polyether diol compound as the polyol compound in order to obtain good printability in a system that does not contain aromatic hydrocarbon organic solvents (toluene, etc.) and contains a large proportion of highly polar organic solvents such as alcohols and esters. When other solvents are used, it may be preferable to use a polyester diol compound.
[0077] Furthermore, it is also possible to utilize a polyurethane resin obtained by using a chain extender or a reaction terminator. Examples of the chain extender include aliphatic diamines such as ethylenediamine, propylenediamine, tetramethylenediamine, and hexamethylenediamine; alicyclic diamines such as isophoronediamine and 4,4'-dicyclohexylmethanediamine; polyamines such as diethylenetriamine and triethylenetetratriamine; aromatic diamines such as toluylenediamine; aromatic aliphatic diamines such as xylenediamine; diamines having a hydroxyl group such as N-(2-hydroxyethyl)ethylenediamine, N-(2-hydroxyethyl)propylenediamine, and N,N'-di(2-hydroxyethyl)ethylenediamine; and diol compounds such as ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, diethylene glycol, and triethylene glycol.
[0078] Examples of the reaction terminator include monoalcohols such as methanol and ethanol, alkylamines such as n-propylamine, n-butylamine, and di-n-butylamine, alkanolamines such as monoethanolamine and diethanolamine, aliphatic diamines such as ethylenediamine, propylenediamine, tetramethylenediamine, and hexamethylenediamine, alicyclic diamines such as isophoronediamine, 1,4-butanediamine, and 4,4'-dicyclohexylmethanediamine, polyamines such as diethylenetriamine and triethylenetetratriamine, aromatic diamines such as toluylenediamine, aromatic aliphatic diamines such as xylylenediamine, diamines having a hydroxyl group such as N-(2-hydroxyethyl)ethylenediamine, N-(2-hydroxyethyl)propylenediamine, and N,N'-di(2-hydroxyethyl)ethylenediamine, and aminoethylethanolamine.
[0079] In order to obtain the polyurethane resin used in the present invention using the above synthesis components, first, the NCO of the polyisocyanate compound and the OH of the diol compound are reacted so that the molar equivalent ratio (NCO equivalent of the polyisocyanate compound / OH equivalent of the diol compound) is 0.5 or more and 3.0 or less, preferably 1.2 or more and 1.5 or less, and then, if necessary, a chain extender and a reaction terminator are reacted. If the NCO equivalent of the polyisocyanate compound / the OH equivalent of the diol compound is less than 0.5, the heat resistance and oil resistance tend to decrease, whereas if the NCO equivalent of the polyisocyanate compound / the OH equivalent of the diol compound is more than 3, the stretchability tends to decrease.
[0080] (Biomass polyurethane) In consideration of environmental aspects, a part or all of the diol compounds constituting the polyurethane may be diol compounds obtained using biomass components derived from plant components. As such a diol compound, a polyester polyol compound is preferable, and as the polyester polyol compound, a biopolyester polyol obtained by reacting a short-chain diol compound having 2 to 4 carbon atoms with a carboxylic acid compound can be used. As for the biopolyol component, it is more preferable that at least one of the short-chain diol compound and the carboxylic acid compound is derived from a plant, and it is even more preferable that both are derived from a plant. The plant-derived short-chain diol compound having 2 to 4 carbon atoms is not particularly limited. For example, the short-chain diol compound may be 1,3-propanediol, 1,4-butanediol, ethylene glycol, etc., which are obtained from plant raw materials by the following method. These may be used in combination. 1,3-propanediol can be produced from glycerol via 3-hydroxypropylaldehyde (HPA) by a fermentation method in which glucose is obtained by decomposing plant resources (such as corn, etc.). The 1,3-propanediol component produced by a biomethod such as the fermentation method is safer than the 1,3-propanediol component of the EO production method, and useful by-products such as lactic acid can be obtained, and the production cost can be kept low. 1,4-butanediol can be produced by producing glycol from plant resources, fermenting it to obtain succinic acid, and hydrogenating it. Ethylene glycol can also be produced from bioethanol obtained by a conventional method via ethylene.
[0081] The carboxylic acid compound derived from a plant is not particularly limited. For example, the carboxylic acid compound is sebacic acid, succinic acid, lactic acid, glutaric acid, dimer acid, etc. These may be used in combination. Among these, the carboxylic acid compound preferably contains at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid. In addition, 0.05 to 0.5 parts by mass of malic acid may be contained per 100 parts by mass of sebacic acid. The biopolyester polyol compound is produced as a 100% plant-derived biopolyester polyol by appropriately condensing a plant-derived short-chain diol compound and a plant-derived carboxylic acid. Specifically, polytrimethylene sebacate polyol is obtained by directly dehydrating and condensing plant-derived sebacic acid and plant-derived 1,3-propanediol. Also, polybutylene succinate polyol is obtained by directly dehydrating and condensing plant-derived succinic acid and plant-derived 1,4-butanediol. One or more of these biopolyester polyol compounds may be used. The urethane prepolymer obtained from these plant-derived components may be contained in an amount of 10% by mass or more, or 40% by mass or more, calculated as a solid content, in the total urethane prepolymer. Even when a plant-derived component is used in this way, the same chain extenders and reaction terminators as described above can be used.
[0082] (Polyamide resin) The polyamide resin is obtained by reacting an acid component, which may mainly contain polymerized fatty acid, and further may contain aliphatic, alicyclic, and aromatic dicarboxylic acids and aliphatic monocarboxylic acids, with an amine component, which may mainly contain aliphatic, alicyclic, araliphatic, and aromatic polyamines alone or in mixtures, and further may contain primary and secondary monoamines. Here, the polymerized fatty acid is generally obtained by polymerization of unsaturated fatty acids having 16 to 22 carbon atoms or their esters, and includes monobasic fatty acids, dimerized polymerized fatty acids, trimerized polymerized fatty acids, etc. Examples of aliphatic dicarboxylic acids include succinic acid, adipic acid, azelaic acid, maleic acid, etc. Examples of alicyclic dicarboxylic acids include cyclohexanedicarboxylic acid, etc. Examples of aromatic dicarboxylic acids include isophthalic acid, terephthalic acid, etc. Examples of aliphatic monocarboxylic acids include acetic acid, stearic acid, oleic acid, linoleic acid, etc.
[0083] On the other hand, among the amine components, examples of the aliphatic polyamines include aliphatic diamines such as ethylenediamine, propylenediamine, hexamethylenediamine, and methylaminopropylamine, and aliphatic polyamines such as diethylenetriamine and triethylenetetramine. Examples of the alicyclic polyamines include cyclohexylenediamine and isophoronediamine. Examples of the aromatic aliphatic polyamines include xylylenediamine, and examples of the aromatic polyamines include phenylenediamine and diaminodiphenylmethane. Examples of the primary and secondary monoamines include butylamine, octylamine, diethylamine, monoethanolamine, monopropanolamine, diethanolamine, dipropanolamine, and the like. Examples include amines. From the viewpoints of oil resistance, heat resistance and PVC blocking resistance of the printing ink composition, it is preferable to use a polyamide resin which uses an alkanolamine as the primary or secondary monoamine component and has a hydroxyl group in the molecule. In the method for synthesizing a polyamide resin from the above-mentioned acid component and amine component, it is preferable that the ratio of carboxyl groups / amino groups in the reaction components is 0.9 / 1.0 to 1.0 / 0.9, more preferably 1.0 / 1.0, the reaction temperature is preferably 160 to 280°C, even more preferably 180 to 230°C, and the reaction is carried out under reduced pressure of about 100 torr in the final stage.
[0084] (Thermoplastic polyamide resin using vegetable oil fatty acid as a reaction raw material) Among the above polyamide resins, the thermoplastic polyamide resins using vegetable oil fatty acids as reaction raw materials are not particularly limited. For example, the thermoplastic polyamide resins using vegetable oil fatty acids as reaction raw materials include polyamide resins using vegetable oil fatty acids such as tall oil, rice bran oil, palm oil, coconut oil, soybean oil, etc. as reaction raw materials. By using vegetable oil fatty acids as reaction raw materials, the environmental load when using such thermoplastic polyamide resins can be reduced. The thermoplastic polyamide resin using vegetable oil fatty acid as a reaction raw material is a polycondensation product of polycarboxylic acid containing vegetable oil fatty acid and polyamine. The polyamine is not particularly limited. For example, the polyamine is an aliphatic polyamine, an alicyclic polyamine, an aromatic polyamine, etc. The aliphatic polyamine is ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexane, piperazine, N-aminoethylpiperazine, etc. The alicyclic polyamine is isophoronediamine, bisaminomethylcyclohexane, etc. The aromatic polyamine is metaxylenediamine, etc. The thermoplastic polyamide resin may be used in combination. The number average molecular weight (Mn) of the thermoplastic polyamide resin is not particularly limited. For example, the Mn of the thermoplastic polyamide resin is preferably 1,000 or more. Also, the Mn is preferably 30,000 or less. When the Mn of the thermoplastic polyamide resin is less than 1,000, the printing ink composition tends to have reduced blocking resistance and heat resistance. On the other hand, when the Mn exceeds 30,000, the printing ink composition tends to have reduced crumping resistance. The acid value and amine value of the thermoplastic polyamide resin are not particularly limited. For example, the acid value of the thermoplastic polyamide resin is preferably 10.0 mgKOH / g or less, and the amine value is preferably 5.0 mgKOH / g or less. The softening point of the thermoplastic polyamide resin is more preferably 90 to 150°C. The content of the thermoplastic polyamide resin is not particularly limited. For example, the content of the thermoplastic polyamide resin is preferably 20.0 mass % or more and 70.0 mass % or less based on the total solid content in the printing ink composition.
[0085] (Acrylic resin) The acrylic resin can be produced by a conventionally known method, and the production method is not particularly limited. The acrylic resin is obtained by polymerizing a monomer having a carbon-carbon unsaturated double bond in one molecule in a solvent in the presence of a polymerization initiator. Examples of the monomer having a carbon-carbon unsaturated double bond in one molecule include (i) (meth)acrylic acid derivatives, (ii) aromatic vinyls, (iii) olefinic hydrocarbons, (iv) vinyl esters, (v) vinyl halides, and (vi) vinyl ethers.
[0086] (i) Examples of (meth)acrylic acid derivatives include (meth)acrylonitrile, (meth)acrylate salts, alkyl (meth)acrylates such as methyl (meth)acrylate, butyl (meth)acrylate, ethylhexyl (meth)acrylate, and stearyl (meth)acrylate, and benzyl (meth)acrylate. (ii) Examples of aromatic vinyls include styrenes in which some hydrogen atoms have been substituted with fluorine, such as styrene, methylstyrene, ethylstyrene, chlorostyrene, monofluoromethylstyrene, difluoromethylstyrene, and trifluoromethylstyrene. (iii) Examples of olefinic hydrocarbons include ethylene, propylene, butadiene, isobutylene, isoprene, and 1,4-pentadiene. (iv) Vinyl esters include vinyl acetate, etc. (v) Vinyl halides include vinyl chloride, vinylidene chloride, and the like. (vi) Examples of vinyl ethers include vinyl methyl ether. In addition, as the monomer having a carbon-carbon unsaturated double bond in one molecule, a monomer having a crosslinkable functional group can be used. Examples of the monomer having a functional group include (vii) a monomer having a hydroxyl group, (viii) a monomer having an isocyano group, and (ix) a monomer having an epoxy group.
[0087] (vii) Examples of monomers having a hydroxyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, etc.; glycol mono(meth)acrylates such as polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polytetramethylene glycol mono(meth)acrylate, etc.; and hydroxystyrene. (viii) Examples of monomers having an isocyano group include (meth)acryloyloxyethyl isocyanate, (meth)acryloyloxypropyl isocyanate, and the like, as well as those obtained by reacting a hydroxyalkyl (meth)acrylate, such as 2-hydroxyethyl (meth)acrylate or 4-hydroxybutyl (meth)acrylate, with a polyisocyanate, such as toluene diisocyanate or isophorone diisocyanate. (ix) Examples of monomers having an epoxy group include glycidyl methacrylate, glycidyl cinnamate, glycidyl allyl ether, glycidyl vinyl ether, vinylcyclohexane monoepoxide, and 1,3-butadiene monoepoxide. If necessary, one or more of these monomers having a carbon-carbon unsaturated double bond in one molecule can be used, and the acid value is preferably set to 100 to 200 mgKOH / g. If it is outside this range, phase separation, viscosity increase, and gelation of the printing ink occur, resulting in problems with storage stability. As the polymerization initiator used in synthesizing the acrylic resin, a typical peroxide or azo compound, for example, benzoyl peroxide, azoisobutylvalenonitrile, azobisisobutyronitrile, di-t-butyl peroxide, t-butyl perbenzoate, t-butyl peroctoate, cumene hydroxyperoxide, or the like, is used, and the polymerization temperature is 50 to 140°C, preferably 70 to 140°C. The mass average molecular weight of the resulting polymer is preferably 5,000 to 100,000. The non-aromatic solvent used in the above production method may be ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc., ethers such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, etc., esters such as ethyl acetate, butyl acetate, etc. The solvent may be a mixture of two or more kinds.
[0088] (rosin resin and its derivatives) The rosin-based resin can be arbitrarily selected from rosins and their derivatives that can be used in the reverse printing described above. Among them, the rosin resin preferably has an acid value of 10 to 350 mgKOH / g, more preferably 200 to 350 mgKOH / g, and further preferably 250 to 350 mgKOH / g. Among the rosin resins, rosin maleic acid resin and / or polymerized rosin are preferred. The content of the rosin resin in the printing ink composition is preferably 0.1 to 5.0% by mass.
[0089] (Other resins) Other resins that may be used as necessary in the surface printing ink composition include vinyl chloride / vinyl acetate resin, dimer acid resin, rosin resin, maleic acid resin, petroleum resin, terpene resin, ketone resin, dammar resin, copal resin, chlorinated polypropylene, oxidized polypropylene, etc. By using these hard resins, it is expected that the adhesion will be improved, especially for resin films that have not been surface-treated. The appropriate content of hard resins in the gravure printing ink composition is less than 5.0% by mass. However, when using vinyl chloride-vinyl acetate resin, the solid content ratio of polyurethane resin to vinyl chloride-vinyl acetate resin is preferably polyurethane resin / vinyl chloride-vinyl acetate resin=100 / 0 to 70 / 30, and more preferably 100 / 0 to 10.
[0090] (Chelating Crosslinker) As the chelate crosslinking agent, a metal chelate crosslinking agent such as a titanium chelate or a zirconium chelate can be used. Examples of titanium chelates include titanium alkoxides such as tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, a reaction product of tetraisopropoxytitanium with 2-ethylhexanoic acid, tetramethyl titanate, and tetrastearyl titanate, triethanolamine titanate, titanium acetylacetate, titanium ethylacetoacetate, titanium lactate, octylene glycol titanate, titanium tetraacetylacetonate, n-butyl phosphate titanium, and propanedioxytitanium bis(ethyl acetylacetate). Examples of zirconium chelates include zirconium propionate and zirconium acetylacetate. From the environmental viewpoint, among the chelating crosslinking agents, a chelating crosslinking agent that does not have acetylacetonate as a ligand is preferred so as not to generate acetylacetone after the crosslinking reaction.
[0091] (Fatty acid amide) From the viewpoint of blocking resistance, fatty acid amide is used. Examples of fatty acid amide include saturated fatty acid amide, unsaturated fatty acid amide, modified fatty acid amide, etc., and it is particularly preferable to use modified fatty acid amide in order to improve blocking resistance to soft polyvinyl chloride sheets used for tablecloths. The content of fatty acid amide when it is contained is preferably 0.1 to 3.0 mass %, more preferably 0.5 to 2.0 mass % in the printing ink composition. If the content is less than 0.1% by mass, blocking resistance may decrease, whereas if it exceeds 3.0% by mass, oil resistance may decrease.
[0092] (Organic solvent) As the solvent component used in the printing ink composition for front printing to form the front printing layer, a solvent that can be used in the printing ink composition for back printing can be adopted. Furthermore, as the organic solvent, it is preferable to use an organic solvent that does not contain an aromatic hydrocarbon organic solvent in consideration of the environment. Examples of organic solvents that do not contain an aromatic hydrocarbon organic solvent include alcohol organic solvents such as methanol, ethanol, n-propanol, isopropanol, butanol, ketone organic solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, ester organic solvents such as methyl acetate, ethyl acetate, propyl acetate, butyl acetate, aliphatic hydrocarbon organic solvents such as n-hexane, n-heptane, n-octane, and alicyclic hydrocarbon organic solvents such as cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, cyclooctane, and can be used in a mixture in consideration of the solubility and drying properties of the binder resin. However, in consideration of the environmental aspect, it is preferable to suppress ketone organic solvents as much as possible among the above organic solvents. The amount of these organic solvents used is preferably 15.0% by mass or more in the printing ink composition of the present invention, taking printability into consideration. From the viewpoint of printability, it is preferable to contain propyl acetate in the printing ink composition more preferably 5.0% by mass or more, and even more preferably 10.0% by mass or more. In order to improve printability, it is preferable to contain 0.1 to 10% by mass of water in the organic solvent.
[0093] <Pigments> The above-mentioned pigments can be contained in the surface printing ink composition.
[0094] (Other materials) For the purpose of improving the abrasion resistance, wax may be added to the surface printing ink composition within the range that does not deteriorate the performance. As the wax, various known waxes such as polyolefin wax and paraffin wax can be used. Furthermore, various printing ink additives such as pigment dispersants, leveling agents, surfactants, plasticizers, etc. may be added as desired.
[0095] (Method for producing surface printing ink composition) As a method for producing a printing ink composition for front printing using these materials, a method similar to the method for producing the printing ink composition for reverse printing described above can be adopted.
[0096] (Printing method using surface printing ink composition and laminate obtained thereby) Next, a method for obtaining a surface-printed matter using the surface-printing ink composition will be described. A removable primer layer is formed on a resin substrate for surface printing using the removable primer composition of the present invention. Then, in-line or off-line printing is performed using a surface printing ink composition by a normal surface printing method. The printing speed and drying temperature at this time can be appropriately selected from known speeds and temperatures. As the resin substrate, the above-mentioned substrate for reverse printing can be used.
[0097] <<Printing for shrink packaging>> The ink composition for shrink packaging contains the above-mentioned pigment, a binder resin and various additives.
[0098] <Binder resin> Examples of binder resins that can be used include printing ink compositions for shrink packaging that contain a carboxyl-containing acrylic resin, a cellulose resin, a rosin resin and its derivatives, and a urethane resin, which satisfy the following conditions 1 and 2. Condition 1: The ratio of the solid content mass of the carboxyl group-containing acrylic resin to the solid content mass of the cellulose resin is 80 / 20 to 60 / 40. Condition 2: The rosin resin and its derivatives have an acid value of 150 mgKOH / g or less, and are contained in the resin solid content in the range of 1 to 6 mass %. The printing ink composition for shrink packaging of the present invention will be specifically described below. The biomass degree of the printing ink composition for shrink packaging of the present invention is preferably 10 or more. The biomass degree is calculated using the following formula: Biomass ratio = Biomass content / Total solids including pigment in shrink packaging printing ink composition × 100 Biomass components: Total weight of biomass-derived components in resin solids and additive solids (resin weight x biomass weight ratio + additive weight x biomass weight ratio)
[0099] (Acid value) In the present invention, the acid value is calculated by calculating the theoretical neutralization amount of potassium hydroxide (KOH) for the amount of each monomer theoretically required to obtain 1 g of a carboxyl group-containing acrylic resin, rosin resin, etc., and the total number of neutralization amounts in mg is defined as the acid value of the polymer.
[0100] <Mass average molecular weight> The mass average molecular weight of the resin in the present invention can be measured by gel permeation chromatography (GPC). For example, chromatography is performed using a GPC device Water2690 (Waters) and a column PLgel, 5μ, MIXED-D (Polymer Laboratories) under the following conditions: tetrahydrofuran as developing solvent, column temperature 25°C, flow rate 1 milliliter / min, RI detector, sample injection concentration 10 milligram / milliliter, injection amount 100 microliter, and the mass average molecular weight is calculated as polystyrene equivalent.
[0101] (Carboxyl-containing acrylic resin) Examples of the carboxyl group-containing acrylic resin include copolymers of a radically polymerizable carboxylic acid monomer and a radically polymerizable acrylic monomer, and copolymers containing a radically polymerizable monomer other than the radically polymerizable carboxylic acid monomer and the radically polymerizable acrylic monomer. Examples of the radical polymerizable carboxylic acid monomer include acrylic acid, methacrylic acid, crotonic acid; monoesters and monoamides of dicarboxylic acids such as maleic acid, fumaric acid, citraconic acid, and itaconic acid; maleic anhydride, citraconic anhydride, and itaconic anhydride; and esters of vinyl alcohol and saturated carboxylic acids having 2 to 18 carbon atoms such as acetic acid, propionic acid, lauric acid, and stearic acid.
[0102] Examples of the radically polymerizable acrylic monomer include alcohol esters of acrylic acid or methacrylic acid such as methyl, ethyl, propyl, butyl, and pentyl alcohol, and diesters such as ethylene glycol and propylene glycol. Examples of the radically polymerizable monomer (c) other than the radically polymerizable carboxylic acid monomer and the radically polymerizable acrylic monomer include styrene and α-methylstyrene. Among these carboxyl group-containing acrylic resins, copolymers in which the carboxyl group is derived from a methacrylic acid monomer are preferred, and copolymers of methacrylic acid (MAA), methyl methacrylate (MMA) and butyl methacrylate (BMA) are more preferred.
[0103] The acid value of the carboxyl group-containing acrylic resin obtained by copolymerizing the above monomers is preferably 2 to 20 mgKOH / g. It is more preferably 3 mgKOH / g or more, more preferably 15 mgKOH / g or less, and even more preferably 10 mgKOH / g or less. If it is less than 2 mgKOH / g, compatibility with the cellulose resin is likely to be a problem, and if it is more than 20 mgKOH / g, the content resistance (surfactant resistance, alkali resistance) tends to be poor. The mass average molecular weight of the carboxyl group-containing acrylic resin is preferably 30,000 to 100,000. Of these, it is more preferably 35,000 or more, and even more preferably 40,000 or more. It is more preferably 90,000 or less, and even more preferably 80,000 or less. If the mass average molecular weight is less than 30,000, blocking properties, adhesive properties, etc. tend to decrease, whereas if it exceeds 100,000, solubility and solubility with cellulose resins tend to decrease. The content of the carboxyl group-containing acrylic resin in the solid content of the printing ink composition for shrink packaging of the present invention is preferably 10.0% by mass or more, more preferably 13.0% by mass or more, and even more preferably 14.0% by mass or more, and is preferably 40.0% by mass or less, more preferably 35.0% by mass or less, and even more preferably 30.0% by mass or less.
[0104] (Cellulose resin) As the cellulose resin, cellulose acetate propionate resin, cellulose acetate butyrate resin, nitrocellulose resin, etc., which have been conventionally used in gravure ink compositions, can be used. From the viewpoint of improving surfactant resistance, alkali resistance, etc., cellulose acetate propionate resin and cellulose acetate butyrate resin are preferred. The cellulose resin in the printing ink composition for shrink packaging of the present invention satisfies the following condition 1: In the printing ink composition for shrink packaging, the ratio of the solid content mass of the carboxyl group-containing acrylic resin to the solid content mass of the cellulose resin is 80 / 20 to 60 / 40 (solid content mass of carboxyl group-containing acrylic resin / solid content mass of cellulose resin) and is preferably 75 / 25 to 65 / 35. If the solid content mass ratio of the cellulose resin is more than 40, the content resistance (surfactant resistance, alkali resistance) tends to decrease, while if it is less than 20, blocking properties and the like tend to decrease. The total content of the cellulose resins in the solid content of the printing ink composition for shrink packaging of the present invention is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 7.0% by mass or more, and is preferably 20.0% by mass or less, more preferably 15.0% by mass or less, and even more preferably 11.0% by mass or less.
[0105] (Cellulose acetate propionate resin) As the cellulose acetate propionate resin, a known cellulose acetate propionate resin that has been conventionally used in gravure printing ink compositions can be used. Cellulose acetate propionate resin is obtained by triesterifying cellulose with acetic acid and propionic acid, followed by hydrolysis. Generally, commercially available cellulose acetate propionate resins have an acetyl group content of 0.6 to 2.5% by weight, a propionate group content of 42.0 to 46.0% by weight, and a hydroxyl group content of 1.8 to 5.0% by weight. Among these, it is preferable to use a low molecular weight resin in order to improve the biomass content. The content of the cellulose acetate propionate resin in the solid content of the printing ink composition for shrink packaging of the present invention is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 7.0% by mass or more, and is preferably 20.0% by mass or less, more preferably 15.0% by mass or less, and even more preferably 11.0% by mass or less.
[0106] (Cellulose acetate butyrate resin) The cellulose acetate propionate resin may be a resin that has been used in conventional gravure printing ink compositions. The cellulose acetate butyrate resin is obtained by triesterifying cellulose with acetic acid and butyric acid, followed by hydrolysis. Generally, resins with 2 to 30% by weight of acetylation, 17 to 53% by weight of butyrylation, and 1 to 5% of hydroxyl groups are commercially available. Among these, it is preferable to use a low molecular weight resin in order to improve the biomass degree. The content of the cellulose acetate butyrate resin in the solid content of the printing ink composition for shrink packaging of the present invention is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 7.0% by mass or more, and is preferably 20.0% by mass or less, more preferably 15.0% by mass or less, and even more preferably 11.0% by mass or less.
[0107] (nitrocellulose resin) As the nitrocellulose resin, a nitrocellulose resin that has been used in a gravure printing ink composition can be used. The nitrocellulose resin is obtained as a nitric acid ester in which three hydroxyl groups in a six-membered ring of an anhydrous glucopyranose group in the natural cellulose are replaced with nitric acid groups by reacting the natural cellulose with nitric acid. As the nitrocellulose resin used in the present invention, one having a nitrogen content of 10 to 13% and an average degree of polymerization of 35 to 90 is preferably used. Specific examples include SS1 / 2, SS1 / 4, SS1 / 8, TR1 / 16, NCRS-2, (KOREA CNC LTD), etc. The content of the nitrocellulose resin in the solid content of the printing ink composition for shrink packaging of the present invention is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 7.0% by mass or more, and is preferably 20.0% by mass or less, more preferably 15.0% by mass or less, and even more preferably 11.0% by mass or less.
[0108] (Rosin resin and its derivatives) The rosin-based resin and its derivatives can be arbitrarily selected from the rosins and their derivatives that can be used in the reverse printing described above. The acid value of the rosin resin and its derivatives is preferably 150 mgKOH / g or less. If it exceeds 150 mgKOH / g, the stability and content resistance (alkali resistance and surfactant resistance) of the ink composition may decrease. From the viewpoint of even better content resistance, it is more preferably 100 mgKOH / g or less, even more preferably 50 mgKOH / g or less, even more preferably 30 mgKOH / g or less, extremely preferably 20 mgKOH / g or less, and most preferably 10 mgKOH / g or less. The content of the rosin resin and its derivatives in the solid content of the printing ink composition for shrink packaging of the present invention is preferably 3.0 to 20.0 mass%, more preferably 5.0 mass% or more, and even more preferably 7.0 mass% or more, and more preferably 15.0 mass% or less, and even more preferably 10.0 mass% or less.
[0109] (Other resins) In the printing ink composition for shrink packaging of the present invention, other resins may be used in combination as resin components other than the carboxyl group-containing acrylic resin, cellulose resin, rosin resin and derivatives thereof, as necessary, within a range that does not impair the effects of the present invention. Other resins include polyurethane urea resin, polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, polyamide resin, acrylic resin, ethylene-vinyl acetate copolymer resin, chlorinated olefin resin, alkyd resin, vinyl acetate resin, ketone resin, polybutyral resin, cyclized rubber resin, chlorinated rubber resin, petroleum resin, olefin resin, polyester resin, polylactic acid resin, etc. The acrylic resin having a phosphoric acid group may or may not be contained.
[0110] (Pigments) The printing ink composition for shrink packaging can contain the above pigment.
[0111] (Plasticizer) As the plasticizer, dioctyl sebacate, fatty acid triglyceride, ethyl toluenesulfonamide, acetyl tributyl citrate, 2-ethylhexyl stearate, 2-ethylhexyl palmitate, etc., which have been conventionally used in gravure printing inks, and epoxidized vegetable oils can be used. Among these, epoxidized vegetable oils such as epoxidized soybean oil and epoxidized linseed oil are preferred from the viewpoints of content resistance (surfactant resistance, alkali resistance) and biomass degree. The content of the plasticizer is not particularly limited. For example, the content of the plasticizer in the shrink packaging printing ink composition is preferably 0.05% by mass or more, more preferably 0.5% by mass or more, and is preferably 5.0% by mass or less, more preferably 3.0% by mass or less. When the content of the plasticizer is within the above range, the shrink packaging printing ink composition obtained has improved content resistance (surfactant resistance, alkali resistance).
[0112] (amide compounds) Further, it is preferable that the shrink packaging printing ink composition contains an amide compound in order to further improve scratch resistance, adhesion to the substrate, abrasion resistance, and content resistance (surfactant resistance and alkali resistance). Examples of the amide compound include palmitic acid amide, stearic acid amide, ethylene bis oleic acid amide, and hexamethylene bis oleic acid amide, which may be used alone or in combination of two or more. When an amide compound is added, it is preferable that the shrink packaging printing ink composition contains the amide compound in an amount of 0.1 to 5.0% by mass. In particular, it is preferable that the shrink packaging printing ink composition contains the amide compound in an amount of 0.1 to 4.0% by mass, and more preferably in an amount of 0.3 to 2.5% by mass, in order to achieve both scratch resistance, adhesion to the substrate, abrasion resistance, surfactant resistance, and alkali resistance.
[0113] (Solvent component) As the solvent component used in the printing ink composition for shrink packaging which forms the printing layer in the present invention, the solvents which can be used in the ink composition for reverse printing described above can be used. Among these solvent components, from an environmental point of view, it is preferable to use an alcohol-based solvent and / or an ester-based solvent, more preferably an alcohol-based solvent and / or an ester-based solvent having 1 to 4 carbon atoms. Furthermore, it is preferable to use an alcohol-based solvent and an ester-based solvent having 1 to 4 carbon atoms in a mass ratio of alcohol / ester=60 / 40 to 80 / 20, more preferably 63 / 37 to 75 / 25. If the ester-based solvent is more than 40, it may attack the shrink OPS (shrinkable untreated polystyrene film). Also, if the ester-based solvent is less than 20, the solubility of the resin component tends to decrease.
[0114] (Other ingredients) In addition, the printing ink composition for shrink packaging of the present invention may contain, as necessary, abrasion resistance enhancing agents, antiblocking agents, pigment dispersants, antistatic agents, lubricants, crosslinking agents, defoamers, drying regulators, other plasticizers, tackifiers, adhesion improvers, leveling agents, antioxidants, etc. Among these, additives derived from biomass are particularly preferable. As the lubricant, polyethylene (PE) wax, polypropylene wax, PTFE-based wax, paraffin wax, microcrystalline wax, Fischer-Tropsch wax, montan wax, carnauba wax, shellac wax, amide wax, organic polymers, beeswax, mixed waxes of these, and the like are preferred, and among these, polyethylene wax and polypropylene wax are more preferred.
[0115] (Method for producing shrink printing ink composition) As a method for producing a shrink printing ink composition using these materials, the same method as the above-mentioned method for producing a reverse printing ink composition can be adopted.
[0116] (Printing method using shrink printing ink composition and laminate obtained thereby) Next, a method for obtaining a shrink print using the shrink printing ink composition will be described. The release primer composition is applied to a resin substrate for shrink printing to form a release primer layer. Then, shrink printing is performed in-line or off-line using a normal printing method with the shrink printing ink composition. The printing speed and drying temperature at this time can be appropriately selected from known speeds and temperatures. As the resin substrate, the above-mentioned substrate for reverse printing can be used.
[0117] <<Printing on the paper base side of laminated paper>> The printing ink composition used for printing on the paper base side of the laminate paper may be, for example, a water-based flexographic printing ink composition, which contains the above-mentioned pigment, a binder resin, and various additives.
[0118] <Binder resin> The binder that can be used is not particularly limited as long as it is a resin obtained by polymerizing a monomer having an unsaturated double bond used in a normal aqueous flexographic printing ink composition, or a resin obtained by a reaction between functional groups. Specifically, various binder resins such as water-soluble acrylic resins copolymerized with acrylic acid or methacrylic acid and its alkyl ester, or styrene as the main monomer component, water-soluble styrene-acrylic resins, water-soluble styrene-maleic acid resins, water-soluble styrene-acrylic-maleic acid resins, water-soluble polyurethane resins, and water-soluble polyester resins can be exemplified. The content of the binder resin in the aqueous flexographic printing ink composition is preferably 1 to 20% by weight. (Solvent component) As the solvent component used in the aqueous flexographic printing ink composition for forming the printing layer in the present invention, an aqueous medium can be used. The aqueous medium can be water or a mixture of water and a water-miscible solvent.The water-miscible solvent can be, for example, lower alcohols, polyhydric alcohols, and their alkyl ethers or alkyl esters, and specifically can be, for example, lower alcohols such as methanol, ethanol, normal propanol, isopropanol, etc., polyhydric alcohols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, glycerin, etc., ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monoacetate, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, etc. (Other ingredients) In addition to the components described above, the aqueous flexographic printing ink composition of the present invention may contain various additives, such as a film-forming agent, a pigment dispersant or a pigment dispersing resin, an antiblocking agent, a wetting agent, a viscosity adjuster, a pH adjuster, an antifoaming agent, and a general surfactant, which may be appropriately selected and used as necessary.
[0119] (Method for producing water-based flexographic printing ink composition) A typical method for producing an aqueous flexographic printing ink composition using these materials involves mixing and kneading the pigment, binder resin, and aqueous medium, and then adding and mixing the additives, aqueous medium, and the remaining specified materials. (Printing method using water-based flexographic printing ink composition and laminate obtained thereby) Next, a method for obtaining a printed matter using the water-based flexographic printing ink composition will be described. The detachable primer composition is applied to a resin substrate to form a detachable primer layer, then an adhesive is applied, a paper substrate is laminated, and then flexographic printing is performed on the paper substrate using a normal printing method with an aqueous flexographic printing ink composition. The resin substrate may be made of the above-mentioned polyethylene (PE) or the like. EXAMPLES
[0120] Examples are given below to explain the present invention in more detail, but the present invention is not limited to only these examples. Unless otherwise specified, “%” means “mass %” and “part” means “part by mass”. Also, the figures for the amounts of each material in the tables are also “parts by mass”. The primer composition for desorption used in the examples and comparative examples has a mass composition of the solvent as a mixture of ethanol 8: water 2. Note that it is not limited to this mixture.
[0121] <Examples and Comparative Examples of Back Printing Using a Polyethyleneimine Compound> <Production Example of Polyurethane Resin Varnish (Biomass Polyurethane)> Into a four-necked flask equipped with a stirrer, a cooling tube, and a nitrogen gas inlet tube, 200 parts by mass of a polyester diol having a mass average molecular weight of 2,000 obtained from sebacic acid (derived from castor oil) / succinic acid (derived from plants) = 30 / 70 (mass ratio) and 1,3-propanediol (derived from plants), 17.6 parts by mass of isophorone diisocyanate, and 21.0 parts by mass of hydrogenated MDI were charged, and the reaction was carried out at 100 to 105 °C for 6 hours while introducing nitrogen gas. After allowing to cool to near room temperature, 400 parts by mass of ethyl acetate and 171 parts by mass of isopropyl alcohol were added, then 8.2 parts by mass of isophoronediamine was added for chain extension, and further 0.35 parts by mass of monoethanolamine was added for reaction. Thereafter, 1.3 parts by mass of isophoronediamine and 0.6 parts by mass of diethylenetriamine were added to stop the reaction to obtain a polyurethane resin varnish (solid content 30 mass %, amine value 6.4 mgKOH / g).
[0122] <Production Example of Polyurethane Resin Varnish (Not Biomass Polyurethane)> A four-neck flask equipped with a stirrer, a cooling tube, and a nitrogen gas inlet tube was charged with 100 parts by mass of 3-methyl-1,5-pentylene adipate diol having a number average molecular weight of 2,000, 100 parts by mass of polypropylene glycol having a mass average molecular weight of 2,000, 17.6 parts by mass of isophorone diisocyanate, and 21.0 parts by mass of hydrogenated MDI, and reacted for 6 hours at 100 to 105 ° C. while introducing nitrogen gas. After cooling to near room temperature, 400 parts by mass of ethyl acetate and 171 parts by mass of isopropyl alcohol were added, and then 8.2 parts by mass of isophorone diamine were added to extend the chain, and 0.35 parts by mass of monoethanolamine were added to react, and then 1.3 parts by mass of isophorone diamine and 0.6 parts by mass of diethylene triamine were added to stop the reaction, and a polyurethane resin varnish (solid content 30% by mass, amine value 6.4 mg KOH / g) was obtained.
[0123] <Polyurethane resin varnish obtained by using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound> (Method of producing ketimine solution 1) 51 parts of isophoronediamine, 31.2 parts of N-(2-hydroxyethyl)ethylenediamine, and 174 parts of acetone were mixed and stirred at room temperature for 1 hour, to obtain a ketimine solution 1. (Method of manufacturing polyurethane resin) A four-neck flask equipped with a stirrer, a cooling tube, and a nitrogen gas inlet tube was charged with 400 parts of 3-methyl-1,5-pentylene adipate diol having a number average molecular weight of 4,000, 33.3 parts of isophorone diisocyanate, and 0.04 parts of tetrabutyl titanate, and the mixture was reacted at 90 to 100°C for 6 hours while introducing nitrogen gas. Next, 812 parts of propyl acetate and 203 parts of isopropyl alcohol were added, and the mixture was cooled to near room temperature. 32.29 parts of the above ketimine solution 1 was added and stirred for 20 minutes, and then 3 parts of water was added and stirred for 15 minutes to obtain a polyurethane resin varnish (solid content 30%) with a mass average molecular weight of 35,000 and an amine value of 6.5 mgKOH / g. <Vinyl chloride / vinyl acetate copolymer> Solvine TA-3, Nissin Chemical Industry Co., Ltd. <Rosin and its derivatives> Polymerized rosin: Acid value 160mgKOH / g
[0124] <Chlorinated polypropylene varnish> 40 parts by mass of chlorinated polypropylene (solid content 50%) having a chlorination degree of 40% and a mass average molecular weight of 100,000 and 60 parts by mass of methylcyclohexane were mixed and stirred to obtain a chlorinated polypropylene varnish having a solid content of 20%. <Silica particles> Average particle size: 4.5μm <Polyethylene wax> Average particle size: 2.11μm <Fatty acid amide> Ethylenebisstearamide
[0125] <Production Example of Reverse Printing Ink Composition> 10 parts by mass of pigment (CIPB15:4), 30 parts by mass of each polyurethane resin, and 3 parts by mass of vinyl chloride-vinyl acetate copolymer (Solvine TA-3) were kneaded using Red Devil's paint conditioner, and then 2 parts by mass of chlorinated propylene varnish (solid content 20%), 0.5 parts by mass of polymerized rosin, 0.5 parts by mass of silica particles, 0.2 parts by mass of polyethylene wax, 0.2 parts by mass of ethylene bisstearic acid amide, 51 parts by mass of solvent, and 2 parts by mass of water were added to obtain a printing ink composition for reverse printing.
[0126] (Printing base material) P-2161#25: Biaxially oriented polypropylene film (thickness 25 μm) (Toyobo Co., Ltd.) (Removal primer) Polyethylenimine listed in Table 1 below (trade name Epomin (Nippon Shokubai Co., Ltd.), trade name Lupasol P (BASF))
[0127] [Table 1]
[0128] Number average molecular weight: SP-018 / Number average molecular weight by boiling point elevation (Mn) P-1000, P-3000 / Number average molecular weight by viscosimetry (Mn) Mass average molecular weight: Mass average molecular weight (Mw) by GPC method Amine value: Measured by acid titration using a non-aqueous system Amine ratio: measured by NMR (13C)
[0129] (Reverse printing, lamination, and test results) <Dry laminate 1 (base film: normal film)> Each polyethyleneimine shown in Table 1 was diluted as shown in Table 2 below to form the release primer composition on the treated surface of P-2161#25 in order to obtain the following laminate structure 1, and the composition was applied and dried under the following conditions using a gravure printing machine. 2 ) is the amount of polyethyleneimine. Each reverse printing ink composition was further added with a mixed solvent of normal propyl acetate / isopropyl alcohol = 80 / 20, and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and each diluted ink composition was printed on the surface of each polyethyleneimine under the following conditions using a gravure printing machine and dried to obtain a print. An adhesive (Takelac A-969V / Takelac A-5, solid content 30% by mass) was applied on top of it, and VMCPP was then adhered using a dry laminating machine to create a laminated print of the laminate structure 1 shown below.
[0130] <Dry laminate 2 (base film: transparent vapor deposition film)> Each of the polyethyleneimines shown in Table 1 was diluted as shown in Table 2 below onto the treated surface of each of the transparent vapor-deposited PET or transparent vapor-deposited NY films, and each of the release primer compositions was applied and dried under the following conditions using a gravure printer. The application amounts (g / m2) in Table 2 are shown in Table 2. 2) is the amount of polyethyleneimine. Each reverse printing ink composition was further added with a mixed solvent of normal propyl acetate / isopropyl alcohol = 80 / 20, and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and each diluted ink composition was printed on the surface of each polyethyleneimine under the following conditions using a gravure printing machine and dried to obtain a print. An adhesive (Takelac A-515 / Takelac A-50, solid content 30% by mass) was applied on top of it, and RXC-22#60 was then adhered using a dry laminating machine to create a laminated print of the laminate structure 2 shown below.
[0131] <Extrusion Lamination 1> Each polyethyleneimine shown in Table 1 was diluted as shown in Table 2 below on the treated surface of each film of PET, NY, or transparent vapor-deposited PET or transparent vapor-deposited NY, and each release primer composition was applied and dried under the following conditions using a gravure printer. The application amounts (g / m2) in Table 2 are shown in Table 2. 2 ) is the amount of polyethyleneimine. Each reverse printing ink composition was further diluted with a mixed solvent of normal propyl acetate / isopropyl alcohol = 80 / 20 and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and printed and dried on the surface of each polyethyleneimine under the following conditions to obtain a print. An AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) was applied on top of it, and molten polyethylene was then laminated on top of it using an extrusion laminator to create a laminate print of the following laminate structure 3.
[0132] <Extrusion Lamination 2> Each polyethyleneimine shown in Table 1 was diluted as shown in Table 2 below to form the release primer composition on the treated surface of the OPP film so as to obtain the following laminate structure 4, and the composition was then applied and dried under the following conditions using a gravure printing machine. 2) is the amount of polyethyleneimine. Each reverse printing ink composition was further added with a mixed solvent of normal propyl acetate / isopropyl alcohol = 80 / 20, and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and each diluted ink composition was printed on the surface of each polyethyleneimine under the following conditions using a gravure printing machine and dried to obtain a print. An AC agent (Epomin P-1000, solid content 0.7% by mass) was applied on top of it, and molten polyethylene was further laminated on top of it using an extrusion laminator to create a laminate print of laminate structure 4 shown below.
[0133] (Application conditions for each primer composition for detachment) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate (wet coating amount 6g / m 2 degree) Drying temperature: 70℃
[0134] (Printing conditions for reverse printing ink composition) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 55℃
[0135] [Table 2]
[0136] In the following Examples and Comparative Examples, the results for laminate structure 1 are shown in Table 3, the results for laminate structure 2 in Table 4, the results for laminate structure 3 in Table 5, and the results for laminate structure 4 in Table 6, respectively. Laminated structure 1 : P-2161#25 / polyethyleneimine compounds / printing ink compositions for reverse printing / adhesive (Takelac A-969V / Takelac A-5 solid content 30%) / VMCPP P-2161#25: Biaxially oriented polypropylene film (thickness 25 μm) (Toyobo Co., Ltd.) Adhesive (Takelac A-969V / Takelac A-5): Two-component adhesive, solid content 30% by mass (Mitsui Chemicals) VMCPP: Aluminum-coated non-oriented polypropylene (Toray)
[0137] Laminated structure 2 : Transparent vapor-deposited PET or transparent vapor-deposited NY / polyethyleneimine-based compound / reverse printing ink composition / adhesive (Takelac A-515 / Takelac A-50, solid content 30% by mass) Solid content 30%) / RXC-22#60 Vapor-deposited PET: GL-ARH-F (Toppan Printing Co., Ltd.) Transparent deposition NY: GL-ARH-W (Toppan Printing Co., Ltd.) Adhesive (Takelac A-515 / Takelac A-50): Two-component adhesive, solid content 30% by mass (Mitsui Chemicals) RXC-22#60: Non-oriented propylene film (Mitsui Chemicals Tocello Co., Ltd.)
[0138] Laminated structure 3 : PET or NY or transparent vapor-deposited PET or transparent vapor-deposited NY / polyethyleneimine compounds / reverse printing ink compositions / AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) / molten polyethylene PET: Polyethylene terephthalate film E-5102#12 (Toyobo) NY: Nylon film ON-15#12 (Unitika) Vapor-deposited PET: GL-ARH-F (Toppan Printing Co., Ltd.) Transparent deposition NY: GL-ARH-W (Toppan Printing Co., Ltd.) AC agent (Takelac A-3210 / Takelac A-3072): solid content 7% by mass (Mitsui Chemicals) Molten polyethylene: Sumikasen L705 resin temperature 355℃ (Sumitomo Chemical Co., Ltd.)
[0139] Laminated structure 4 OPP / polyethyleneimine compound / printing ink composition for reverse printing / AC agent (Epomin P-1000, solid content 0.7% by mass) / molten polyethylene OPP film: Corona-discharged biaxially oriented polypropylene film P-2161#25 (Toyobo Co., Ltd.) NY: Nylon film ON-15#12 (Toyobo) AC agent (Epomin P-1000): Polyethyleneimine, solid content 0.7% by mass (Sannihon Shokubai Co., Ltd.) Molten polyethylene: Sumikasen L705 resin temperature 355℃ (Sumitomo Chemical Co., Ltd.)
[0140] <Evaluation of ink release properties> After printing and drying sufficiently, 1.5 g of each of the above printed matter was cut into small pieces of about 15 mm MD×25 mm TD to obtain samples for ink release property testing. (Preparation of Water-Based Release Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of an alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution. (Preheating of the water-based desorption solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of the desorption solution 2 consisting of an alkaline aqueous solution) 100 g of the release solution 2 consisting of an alkaline aqueous solution was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C.
[0141] (Detachment) After each release liquid reached 70°C, each of the ink release test samples was placed in release liquid 1 made of water and release liquid 2 made of an alkaline aqueous solution, and stirred for 60 minutes for release liquid 1 made of water and for 30 minutes for release liquid 2 made of an alkaline aqueous solution using a stainless steel stirring blade with a blade diameter of 25 mm. After stirring, the HDPE (high density polyethylene) container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release liquid and the various film pieces were separated using a stainless steel mesh with mesh openings of approximately 2 mm. (rinse) After removal, each film was transferred to a 200cc HDPE container and 100g of water was added. The mixture was stirred for 5 minutes using a stainless steel stirring blade with a blade diameter of 25mm. After leaving the mixture to stand for 5 minutes, the film pieces were separated from the water using a stainless steel mesh. After drying the film pieces, the releasability of the ink from the films was visually evaluated.
[0142] Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria for laminate structures 1 to 4) ○: The ink coating was completely peeled off from the film as coating pieces. ×: No peeling
[0143] Desorption (hot water) conditions: 70℃ hot water, stirring for 60 minutes (Evaluation criteria for laminate structures 1 to 4) ○: The ink coating was completely peeled off from the film as coating pieces. ×: No peeling
[0144] Tape adhesive strength (for each printed item immediately after printing and drying) To obtain a prescribed coating amount, a gravure printer was used to apply each of the above polyethyleneimines to the treated surfaces of the various films, and each of the release primer compositions was diluted as shown in Tables 3 to 6 below. The gravure printer was used to apply and dry each of the release primer composition compositions under the following conditions. Each of the reverse printing ink compositions was diluted to 16 seconds using a Rigo Zahn Cup No. 3 by adding a mixed solvent of n-propyl acetate / isopropyl alcohol = 80 / 20 to the surface of each of the release primer composition layers, and the reverse printing ink composition was applied to the surface of each of the release primer composition layers under the above conditions using a gravure printer. After printing and drying, each print was obtained. Adhesion was evaluated according to the following criteria based on the degree to which the printed film peeled off when cellophane tape was applied to the printed surface of each of the obtained prints and then quickly peeled off. (Evaluation Criteria) ◯: The area ratio of the printed coating that peeled off from the film was less than 5%. △: 5% or more and less than 30% of the area of the printed coating peeled off from the film. ×: 30% or more of the area of the printed coating peeled off from the film.
[0145] Laminate Strength After each laminate print of Laminate Constructions 1 to 4 was obtained, it was cut to a width of 15 mm, and the T-peel strength was measured using a peel tester manufactured by Yasuda Seiki Seisakusho. (Evaluation criteria for laminate structures 1 and 4) ○: Peel strength is 1.2N / 15mm or more △: Peel strength is 0.7N / 15mm or more and less than 1.2N / 15mm ×: Peel strength is less than 0.7N / 15mm (Evaluation criteria for laminate structure 2, 3) ○: Peel strength is 5N / 15mm or more △: Peel strength is 3N / 15mm or more and less than 5N / 15mm ×: Peel strength is less than 3N / 15mm
[0146] Blocking property Using a gravure printer, each of the release primer compositions, prepared by diluting the polyethyleneimine as shown in Table 3 below, was applied to the treated surface of each film under the following conditions and dried. Each of the release primer composition layers was printed on the surface of the surface using a gravure printer under the following conditions, with each of the release printing ink compositions being further diluted with a normal propyl acetate / isopropyl alcohol = 80 / 20 mixed solvent and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and dried. The printed surface of each printed matter and the untreated surface of each film were combined, and a pressure of 400 g / cm was applied. 2 After leaving the film at 40° C. for 12 hours under a load of 1000 μg / cm2, the blocking resistance was evaluated based on the state of each film when it was peeled off. (Evaluation Criteria) ○: Peels off without resistance and there is no transfer of the ink film △: There is resistance, but the ink film does not transfer at all ×: Transfer of the ink film was observed.
[0147] The following evaluations were the same for each reverse printing ink composition using three types of polyurethane resin varnish (polyurethane resin varnish (biomass polyurethane), polyurethane resin varnish (non-biomass polyurethane), and polyurethane resin varnish obtained using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound). Therefore, the results for polyurethane resin varnish (biomass polyurethane) are shown below.
[0148] [Table 3]
[0149] [Table 4]
[0150] [Table 5]
[0151] [Table 6]
[0152] <Comparative Example Dry Laminate 1 (Base Film: Regular Film)> Each comparative example detachment primer composition was diluted to a prescribed application amount on the treated surface of each film to obtain the comparative example laminate structure 1 below, and then dried under the following conditions using a gravure printer. Each reverse printing ink composition was further diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd. by adding a mixed solvent of n-propyl acetate / isopropyl alcohol=80 / 20 to the reverse printing ink composition, and printed and dried under the following conditions using a gravure printer on the surface of each of the detachment primer composition layers to obtain a print. An adhesive (Takelac A-969V / Takelac A-5, 30% solids) was applied on top of it, and VMCPP was then attached using a dry laminating machine to create a laminated print of the laminate structure 1 shown below.
[0153] <Comparative Example Dry Laminate 2 (Base Film: Transparent Vapor Deposition Film)> Each of the comparative example release primer compositions was diluted to a prescribed amount on the treated surface of each of the transparent vapor-deposited PET or transparent vapor-deposited NY films to obtain the following laminate structure 2, and then coated and dried under the following conditions using a gravure printer to obtain a print. Each of the diluted ink compositions was further diluted with a normal propyl acetate / isopropyl alcohol = 80 / 20 mixed solvent and diluted to 16 seconds using a Rigo Zahn Cup No. 3, and printed and dried under the following conditions using a gravure printer to obtain a print. An adhesive (Takelac A-515 / Takelac A-50, solid content 30% by mass) was applied on top of it, and RXC-22#60 was then adhered using a dry laminating machine to create a laminated print of the laminate structure 2 shown below.
[0154] <Extrusion Laminate 1 of Comparative Example> Each of the comparative example release primer compositions was diluted to a prescribed amount and applied to the treated surface of each of the films, PET, NY, or transparent vapor-deposited PET or transparent vapor-deposited NY, to obtain a print under the following conditions using a gravure printer, followed by drying, to obtain a print, so as to obtain the following laminate structure 3. Each of the diluted ink compositions was further diluted with a mixed solvent of n-propyl acetate / isopropyl alcohol = 80 / 20 and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and printed and dried under the following conditions using a gravure printer, to obtain a print. An AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) was applied on top of it, and molten polyethylene was then laminated on top of it using an extrusion laminator to create a laminate print of the following laminate structure 3.
[0155] <Extrusion Laminate 2 of Comparative Example> Each comparative example of a release primer composition was diluted to a prescribed application amount on the treated surface of an OPP film so as to obtain the following laminate structure 4, and then coated and dried under the following conditions using a gravure printer to obtain a print. Each reverse printing ink composition was further diluted with a normal propyl acetate / isopropyl alcohol = 80 / 20 mixed solvent and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and then printed and dried under the following conditions using a gravure printer to obtain a print. An AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) was applied on top of it, and molten polyethylene was then laminated on top of it using an extrusion laminator to create a laminate print of laminate structure 4 below.
[0156] (Application methods and conditions for each primer composition for detachment in comparative examples) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 70℃
[0157] (Printing method and conditions for reverse printing ink composition) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 55℃
[0158] Comparative Example Laminate Structure 1: P-2161#25 / Comparative Example Detachable Primer Composition / Reverse Printing Ink Composition / Adhesive (Takelac A-969V / Takelac A-5 30% solids) / VMCPP P-2161#25: Biaxially oriented polypropylene film (thickness 25 μm) (Toyobo Co., Ltd.) Adhesive (Takelac A-969V / Takelac A-5): Aromatic ether-based two-component adhesive solid content 30% by mass (Mitsui Chemicals Co., Ltd.) VMCPP: Aluminum-coated non-oriented polypropylene (Toray)
[0159] Comparative example laminate structure 2 : Transparent vapor-deposited PET or transparent vapor-deposited NY / each of the comparative example's detachment primer compositions / each of the reverse printing ink compositions / adhesive (Takelac A-515 / Takelac A-50, solid content 30% by mass) solid content 30% / RXC-22#60 PP Vapor-deposited PET: GL-ARH-F (Toppan Printing Co., Ltd.) Transparent deposition NY: GL-ARH-W (Toppan Printing Co., Ltd.) Adhesive (Takelac A-515 / Takelac A-50): Two-component adhesive, solid content 30% by mass (Mitsui Chemicals) RXC-22#60: Non-oriented propylene film (Mitsui Chemicals Tocello Co., Ltd.)
[0160] Comparative example laminate structure 3 PET or NY or transparent vapor-deposited PET or transparent vapor-deposited NY / each of the comparative example's detachment primer compositions / each of the reverse printing ink compositions / AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) / molten polyethylene PET: Polyethylene terephthalate film E-5102#12 (Toyobo) NY: Nylon film ON-15#12 (Unitika) Vapor-deposited PET: GL-ARH-F (Toppan Printing Co., Ltd.) Transparent deposition NY: GL-ARH-W (Toppan Printing Co., Ltd.) AC agent (Takelac A-3210 / Takelac A-3072): solid content 7% by mass (Mitsui Chemicals) Molten polyethylene: Sumikasen L705 resin temperature 355℃ (Sumitomo Chemical Co., Ltd.)
[0161] Comparative example laminate structure 4 OPP / each of the comparative example's release primer compositions / each of the reverse printing ink compositions / AC agent (Epomin P-1000, solid content 0.7% by mass) / molten polyethylene OPP film: Corona-discharged biaxially oriented polypropylene film P-2161#25 (Toyobo Co., Ltd.) NY: Nylon film ON-15#12 (Toyobo) AC agent (Epomin P-1000): Polyethyleneimine, solid content 0.7% by mass (Sannihon Shokubai Co., Ltd.) Molten polyethylene: Sumikasen L705 resin temperature 355℃ (Sumitomo Chemical Co., Ltd.) (Each of the comparative detachment primer compositions) PVA: Poval 28-98 (polyvinyl alcohol with a saponification degree of 90% or more) (Kuraray Co., Ltd.) General-purpose polyurethane: The polyurethane resin varnish described above (not biomass polyurethane)
[0162] The following evaluations were the same for each reverse printing ink composition using three types of polyurethane resin varnish (polyurethane resin varnish (biomass polyurethane), polyurethane resin varnish (non-biomass polyurethane), and polyurethane resin varnish obtained using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound). Therefore, the results for polyurethane resin varnish (biomass polyurethane) are shown below. The ink releasability, adhesiveness, and laminating strength were evaluated in the same manner and according to the same criteria as described above. However, the ink releasability was tested using an alkaline aqueous solution of the release liquid 2. As the release liquid 2 composed of an alkaline aqueous solution, 2 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, stirred and dissolved to obtain a release liquid composed of an alkaline aqueous solution for use.
[0163] All of the laminating structures 1 to 4 of the comparative examples showed the same results. Therefore, the results for the laminating structure 1 are shown in Table 7 below.
[0164]
Table 7
[0165] When the primer composition for release of the present invention was applied, smooth release was achieved with both water and the alkaline aqueous solution. Also, the adhesiveness, laminating strength, and blocking resistance immediately after printing were excellent. However, according to the results shown in Tables 3 to 7, when the primer composition for release of the present invention was not applied, and when PVA and general-purpose polyurethane were applied, it was not possible to achieve both excellent releasability and laminating strength.
[0166] <Examples of surface printing using a polyethyleneimine compound> (Polyurethane resin varnish) A four-neck flask equipped with a stirrer, a cooling tube, and a nitrogen gas inlet tube was charged with 100 parts by mass of 3-methyl-1,5-pentylene adipate diol having a number average molecular weight of 2,000, 100 parts by mass of polypropylene glycol having a mass average molecular weight of 2,000, 17.6 parts by mass of isophorone diisocyanate, and 21.0 parts by mass of hydrogenated MDI, and reacted for 6 hours at 100 to 105 ° C. while introducing nitrogen gas. After cooling to near room temperature, 523.3 parts by mass of ethyl acetate and 223.8 parts by mass of isopropyl alcohol were added, and then 8.2 parts by mass of isophorone diamine were added to extend the chain, and 0.35 parts by mass of monoethanolamine were added to react, and then 1.3 parts by mass of isophorone diamine and 0.6 parts by mass of diethylene triamine were added to stop the reaction, and a urethane resin (polyurethane resin varnish (solid content 25% by mass)) was obtained.
[0167] (CAB) Cellulose acetate butyrate (Eastman Chemical Company, number average molecular weight 70,000, butyryl degree 35-39%)
[0168] (nitrocellulose) Nitrocellulose (hydrated with 30% water by weight) (NOBEL NC CO., Ltd.) (DLX5-8) (35 parts by mass) was dissolved in a mixed solvent of 58 parts of ethyl acetate and 7 parts of isopropyl alcohol to obtain a nitrocellulose solution with a solid content of 35% by mass.
[0169] (Polyamide resin) Thermoplastic polyamide resin (Mw 8,000, acid value 2, softening point 110℃) made from tall oil fatty acid as a reaction raw material (Polyvinyl chloride) Solvine TA5R (Nissin Chemical Industry Co., Ltd.) (Acrylic resin) Hiros-X·RL-4032 (solid content 40% by mass) (Seiko PMC Corporation) (Polyethylene wax) PA-60 (solid content 25% by mass) (Polycon) (Titanium dioxide) Typec PFR209 (Ishihara Sangyosha)
[0170] <Preparation of printing ink composition> According to the mass ratio (mass%) in Table 8 below, each material was kneaded in a paint conditioner to prepare a printing ink composition. The obtained printing ink composition was subjected to gravure printing under the following conditions to obtain a printed matter. The obtained printed matter was evaluated for adhesion and releasability according to the following evaluation methods.
[0171] <Creating printed matter> The above-mentioned release primer: polyethyleneimine P-1000, diluted to a prescribed coating amount, was applied and dried using a gravure printer under the following conditions on a corona discharge-treated stretched polypropylene film (product name OPP P-2161, 25 μm, manufactured by Toyobo Co., Ltd.). On the surface of each polyethyleneimine layer, each diluted surface printing ink composition, which was prepared by adding each mixed solvent to each surface printing ink composition in Table 8 below and diluting the ink to 16 seconds using Rigo Zahn Cup No. 3, was printed and dried under the following conditions using a gravure printer to obtain each surface printing ink composition print. 1.5 g of each surface printing ink composition print was shredded into small pieces of about 15 mm MD × 25 mm TD to obtain a sample for printing layer peeling test.
[0172] (Method and conditions for applying primer composition for detachment) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 70℃ (Printing method and conditions for surface printing ink composition) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 55℃ The ink releasability and adhesion were evaluated in the same manner and according to the same criteria as described above.
[0173] <Evaluation of adhesion to substrate> Adhesion was evaluated according to the following criteria based on the degree of peeling of the printed film when cellophane tape was applied to the printed surface of each printed matter obtained in the production of the printed matter and then quickly peeled off. Hereinafter, the evaluation of adhesion in this specification was based on this evaluation.
[0174] (Evaluation Criteria) ◯: The area ratio of the printed coating that peeled off from the film was less than 5%. △: 5% or more and less than 30% of the area of the printed coating peeled off from the film. ×: 30% or more of the area of the printed coating peeled off from the film. <Printing layer peeling test method>
[0175] (Preparation of Water-Based Release Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of an alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution.
[0176] (Preheating of Desorption Solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of the desorption solution 2) 100 g of the release solution 2 consisting of an alkaline aqueous solution was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Detachment) After each release liquid reached 70°C, each of the above printed layer peeling test samples was placed in the release liquid and stirred for 60 minutes using a stainless steel stirring blade with a blade diameter of 25 mm for release liquid 1 consisting of water, and for 30 minutes for release liquid 2 consisting of an alkaline aqueous solution. After stirring, the HDPE (high density polyethylene) container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release liquid and the film pieces were separated using a stainless steel mesh with mesh openings of approximately 2 mm. (Rinsing) The film after detachment was transferred to a 200 cc HDPE container, and 100 g of water was added. Stirring was carried out for 5 minutes using a stainless steel stirring blade with a blade diameter of 25 mm. After standing for 5 minutes, the film pieces and water were separated using a stainless steel mesh. After drying the film pieces, the peelability of the ink from the film was visually evaluated.
[0177] Detachment (alkali) conditions: Stirring for 30 minutes in a 2% aqueous sodium hydroxide solution at 70 °C (Evaluation criteria) ○: The ink coating was completely peeled off from the film as a coating piece. ×: Those that did not peel off.
[0178] Detachment (hot water) conditions: Stirring for 60 minutes in hot water at 70 °C (Evaluation criteria) ○: The ink coating was completely peeled off from the film as a coating piece. ×: Those that did not peel off.
[0179]
Table 8
[0180]
Table 9
[0181] When the primer composition for detachment in Table 9 was polyethyleneimine P-1000 coated, in any of the cases of the offset printing ink compositions 1 to 8, detachment was possible even when water or an aqueous alkali solution was used as the detachment liquid, and the adhesion to the corona discharge-treated stretched polypropylene film (product name OPP P-2161, 25 μm, manufactured by Toyobo Co., Ltd.) was also good.
[0182] <A. Examples of shrink printing using a polyethyleneimine compound> (Acrylic resin synthesis) The monomer composition was [n-butyl methacrylate / n-butyl acrylate / 2-hydroxyethyl methacrylate / methyl methacrylate = 35 / 20 / 15 / 30 (mass ratio)], which was polymerized by solution polymerization, and the solvent was evaporated. The mass average molecular weight was 60,000, and the hydroxyl value was 60 mgKOH / g.
[0183] (Production of printing ink composition 1 for shrink packaging) 10.0 parts by mass of pigment (CIPB15:4), 10.0 parts by mass of the above acrylic resin, 3.5 parts by mass of nitrocellulose (product name: LIG 1 / 8, SNPE Japan), 20.0 parts by mass of methylcyclohexane, 35.5 parts by mass of isopropyl alcohol, and 21.0 parts by mass of ethyl acetate were kneaded and dispersed in a conventional manner to produce printing ink composition 1 for shrink packaging.
[0184] (Production of printing ink composition 2 for shrink packaging) 10.0 parts by mass of pigment (CIPB15:4), 9.0 parts by mass of carboxyl group-containing acrylic resin (monomer composition: MAA / MMA / BMA, theoretical acid value 3 mgKOH / g, mass average molecular weight 60,000), 10.0 parts by mass of isopropyl alcohol, and 15.0 parts by mass of ethyl acetate were kneaded using a paint conditioner, and a mixture of 1.2 parts by mass of the carboxyl group-containing acrylic resin, 5.0 parts by mass of cellulose acetate butyrate (CAB-381-0.5, Eastman, number average molecular weight 30,000), 5.0 parts by mass of rosin ester (acid value 7 mgKOH / g), 1.0 part by mass of epoxidized soybean oil, 0.5 parts by mass of stearic acid amide, and Spray 2.2 parts by mass of 30 (Sasol), 0.3 parts by mass of BYK-094 (BYK), 4.5 parts by mass of normal propyl alcohol, 27.4 parts by mass of isopropyl alcohol, and 9.1 parts by mass of ethyl acetate were added and mixed to prepare printing ink composition 2 for shrink packaging.
[0185] (Printing) The above-mentioned release primer composition: polyethyleneimine P-1000, diluted to a prescribed coating amount, was applied and dried on a crystallizable shrinkable PET (polyethylene terephthalate) film using a gravure printer under the following conditions. Each diluted shrink packaging printing ink, which was prepared by adding each of the above-mentioned shrink packaging printing ink compositions to each of the above-mentioned mixed solvents and diluting the ink to 16 seconds using a Rigosha Zahn Cup No. 3, was printed on the surface of each of the polyethyleneimines using a gravure printer under the following conditions and dried to obtain each printed matter. 1.5 g of each of the printed matters of the shrink packaging printing ink compositions was shredded into small pieces of about 15 mm MD × 25 mm TD to obtain samples for printing layer peeling tests. (Method and conditions for applying primer composition for detachment) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 70℃ (Printing method and conditions for printing ink composition for shrink packaging) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 55℃
[0186] <Evaluation of adhesion to substrate> Adhesion was evaluated according to the following criteria based on the degree to which the printed film peeled off when cellophane tape was applied to the printed surface of each of the printed products obtained in the production of the printed products and then quickly peeled off. (Evaluation Criteria) ◯: The area ratio of the printed coating that peeled off from the film was less than 5%. △: 5% or more and less than 30% of the area of the printed coating peeled off from the film. ×: 30% or more of the area of the printed coating peeled off from the film.
[0187] <Printing layer peeling test method> (Preparation of Water-Based Release Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of an alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution.
[0188] (Preheating of Desorption Solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of the desorption solution 2) 100 g of the release solution 2 consisting of an alkaline aqueous solution was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Detachment) After the temperature of the release liquid reached 70°C, the above-mentioned print layer peeling test sample was placed into each release liquid and stirred for 60 minutes using a stainless steel stirring blade with a blade diameter of 25 mm for release liquid 1 consisting of water, and for 30 minutes for release liquid 2 consisting of an alkaline aqueous solution. After stirring, the HDPE container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release liquid and the PET (polyethylene terephthalate) film pieces were separated using a stainless steel mesh with mesh openings of approximately 2 mm. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation Criteria) ○: The ink coating was completely peeled off from the film as coating pieces. ×: No peeling Desorption (hot water) conditions: Stir in 70°C hot water for 60 minutes (Evaluation Criteria) ○: The ink coating was completely peeled off from the film as coating pieces. ×: No peeling
[0189] [Table 10]
[0190] According to Table 10, when polyethyleneimine P-1000 was applied, in both cases of shrink packaging printing ink compositions 1 and 2, desorption was possible using water or an alkaline aqueous solution as the desorbing liquid, and the adhesion to the crystallizable shrink PET film was also good.
[0191] <A. Examples of Printing on the Paper Substrate Side of a Laminated Paper Using a Polyethyleneimine Compound> (Manufacture of an Aqueous Flexographic Printing Ink Composition) <Method for Manufacturing an Aqueous Printing Ink> A mixture of 15 parts by mass of a pigment (phthalocyanine blue, C.I. Pigment Blue 15:3), 15 parts by mass of an alkali-soluble water-soluble resin (Joncryl HPD-671, manufactured by BASF, solid content 25%), 0.5 part by mass of an (ethylene oxide / propylene oxide) block polymer ((EO / PO) block polymer, HLB value 14, Mw 16000), 0.03 part by mass of dibutyl glycol, and 22.97 parts by mass of water was kneaded and dispersed with a bead mill, and then 43.25 parts by mass of a styrene-acrylic resin emulsion (acid value 38 mgKOH / g, glass transition temperature 9 °C, solid content 38.5%), 2.5 parts by mass of polyethylene wax (Chemipar W-100, solid content 35% by mass, manufactured by Mitsui Chemicals, Inc.), and 0.75 part by mass of an antifoaming agent (SN Defoamer 777#C, manufactured by San Nopco Ltd.) were added and mixed to obtain an aqueous flexographic printing ink composition.
[0192] (Production of Printed Matter) Each desorption primer composition obtained by diluting each polyethyleneimine described in Table 1 above to the following Table 2 was applied and dried on a linear low-density polyethylene film (TUX-HC#50, thickness 25 μm, manufactured by Mitsui Chemicals Toagosei Co., Ltd.) using a gravure printing press under the following conditions. An adhesive (Take lac A-969V / Take lac A-5, solid content 30% by mass) was applied thereon, and then a thick matte kraft paper (OK Blizard, 770 g / m 2A laminated paper of the present invention was obtained by adhering a flexographic printing ink composition (Oji Materia Co., Ltd.) to the surface of this paper. The above-mentioned flexographic printing ink composition was applied to the surface of this paper using a 200-line hand proofer and dried to obtain a printed matter. 1.5 g of each of these printed matters was shredded into small pieces of about MD 15 mm × TD 25 mm to obtain samples for the printing layer peeling test. (Method and conditions for applying primer composition for detachment) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 70℃
[0193] Laminate Construction: TUX-HC#50 / polyethyleneimine / adhesive (Takelac A-969V / Takelac A-5 solid content 30%) / OK Blizzard (70g / m2) / flexographic printing ink composition
[0194] <Printing layer peeling test method> (Preparation of Water-Based Release Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of an alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution. (Preheating of Desorption Solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of the desorption solution 2) 100 g of the release solution 2 consisting of an alkaline aqueous solution was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C.
[0195] (Detachment) After the temperature of the release liquid reached 70°C, the above-mentioned print layer peeling test sample was placed into each release liquid and stirred for 60 minutes using a stainless steel stirring blade with a blade diameter of 25 mm for release liquid 1 consisting of water, and for 30 minutes for release liquid 2 consisting of an alkaline aqueous solution. After stirring, the HDPE container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release liquid and the PET (polyethylene terephthalate) film pieces were separated using a stainless steel mesh with mesh openings of approximately 2 mm. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation Criteria) ○: The paper was completely peeled off from the film as a piece of coating. ×: No peeling Desorption (hot water) conditions: 70℃ hot water, stirring for 60 minutes (Evaluation Criteria) ○: The paper was completely peeled off from the film as a piece of coating. ×: No peeling
[0196] Laminate Strength Each of the above printed materials was cut into a width of 15 mm, and the T-peel strength was measured using a peel tester manufactured by Yasuda Seiki Seisakusho Co., Ltd. Hereinafter, the evaluation of adhesion in this specification was carried out based on this evaluation. (Evaluation criteria for laminate structure 1) ○: Peel strength is 1.2N / 15mm or more △: Peel strength is 0.7N / 15mm or more and less than 1.2N / 15mm ×: Peel strength is less than 0.7N / 15mm
[0197] The evaluation results are shown in Table 11 below.
[0198] [Table 11]
[0199] When the detachment primer composition of the present invention was applied, the detachment could be smoothly achieved with either water or an aqueous alkaline solution, and the laminate strength after printing was excellent. However, according to the results shown in Table 11, when the primer composition for desorption of the present invention was not applied, it was impossible to achieve both desorbability and excellent laminate strength.
[0200] <B. Examples and Comparative Examples Using a Mixture Containing a Polyethyleneimine Compound and a Glycidyl Group-Containing Silane Coupling Agent and / or an Isocyanate Group-Containing Silane Coupling Agent> Next, the case of using a primer composition when a silane coupling agent is contained in a polyethyleneimine-based compound will be described. In the primer composition of the present invention, from the viewpoint of improving adhesiveness, a glycidyl group-containing silane coupling agent and an isocyanate group-containing silane coupling agent can be contained. Examples of the glycidyl group-containing silane coupling agent include 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropylmethoxydimethoxysilane, 3-glycidyloxypropylmethoxydiethoxysilane, 3-glycidyloxypropyltriethoxysilane, and the like. Examples of the isocyanate group-containing silane coupling agent include triethoxy(3-isocyanatopropyl)silane and the like. The glycidyl group-containing silane coupling agent and the isocyanate group-containing silane coupling agent are preferably blended so that the ratio of (the number of glycidyl groups + the number of isocyanate groups of the silane coupling agent) to the number of amino groups of the polyethyleneimine-based compound, that is, ((the number of glycidyl groups of the silane coupling agent + the number of isocyanate groups of the silane coupling agent) / the total number of primary amino groups and secondary amino groups of the polyethyleneimine-based compound) is 0.20 to 2.50. And 0.30 or more is more preferable, 0.50 or more is still more preferable, 2.20 or less is more preferable, and 1.90 or less is still more preferable. Note that the number of amino groups is the total number of the number of each of the primary amino group and the secondary amino group. This ratio of (number of glycidyl groups in the silane coupling agent + number of isocyanate groups in the silane coupling agent) / total number of primary amino groups and secondary amino groups in the polyethyleneimine compound can be calculated by the following formula. [(Amount of glycidyl-containing silane coupling agent applied (g / m 2 ) × average number of glycidyl groups in one molecule) / average molecular weight of glycidyl group-containing silane coupling agent (g / mmol)] + [(coating amount of isocyanate group-containing silane coupling agent (g / m 2 ) × average number of isocyanate groups in one molecule) / average molecular weight of isocyanate group-containing silane coupling agent (g / mmol)], [(coating amount of polyethyleneimine compound (g / m 2 ) × amine value (mmol / g) × (average number of primary amino groups + secondary amino groups + tertiary amino groups per molecule) / (average number of primary amino groups + secondary amino groups + tertiary amino groups per molecule)).
[0201] <Removable primer layer> Each detachment primer composition having a solid content concentration of the detachment primer composition shown in Table 12 below was applied and dried under the following conditions using a gravure printer so as to obtain the coating amount shown in Table 13. The coating amount of each component of the detachment primer composition of each Example in Table 13 is the amount of solid content of each component contained in the coating layer per unit area. The solid content concentration of each detachment primer composition is a concentration that becomes a polyethyleneimine-based compound in the coating layer when made into a coating layer, and a concentration that becomes the content of a silane coupling agent having a glycidyl group and a silane coupling agent having an isocyanate group in each coating amount. Furthermore, the ratio of the number of glycidyl groups of the silane coupling agent or the number of glycidyl groups and / or the number of isocyanate groups of the isocyanate group-containing silane coupling agent to the number of amino groups of the polyethyleneimine compound in Table 13 is determined based on the above-mentioned concept, and is the value obtained by dividing the number of glycidyl groups or the number of isocyanate groups in the applied detachment primer composition by the total number of the primary amino groups and the secondary amino groups.
[0202] (Coating Conditions for Each Release Primer Composition) Coating Machine: Gravure Printer Coating Speed: 100 m / min Printing Plate: Solid Plate of Helio 175 line / inch (130°) (Wet Coating Amount is about 6 g / m 2 ) Drying Temperature: 70 °C
[0203] When printing with a gravure printer, after diluting so that the solid content mass % in the release primer becomes as follows, when printing under the conditions of the container with a gravure printer, the following coating amount (g / m 2 ) is obtained.
[0204]
Table 12
[0205]
Table 13
[0206] Hereinafter, examples and comparative examples of printing formats in which a release primer composition containing a silane coupling agent using a mixture containing a B. polyethyleneimine compound, a glycidyl group-containing silane coupling agent, and / or an isocyanate group-containing silane coupling agent are used will be described in the order of printing on the paper substrate side of reverse printing, front printing, shrink printing, and laminated paper in which an adhesive is applied to a base film and a paper substrate is bonded. In addition, for the printing formats in which a release primer composition not containing the silane coupling agent described above is used: reverse printing, front printing, shrink printing, for the same parts of the examples and comparative examples of printing on the paper substrate side of a laminated paper in which an adhesive is applied to a base film and a paper substrate is bonded, they will be omitted.
[0207] <Examples and Comparative Examples of Reverse Printing Using a Mixture Containing a B. Polyethyleneimine Compound, a Glycidyl Group-Containing Silane Coupling Agent, and / or an Isocyanate Group-Containing Silane Coupling Agent> (Dry Lamination) Laminated structure 1 : P-2161#25 / Silane coupling agent + Polyethyleneimine / Reverse printing ink composition / Adhesive (Takelac A-969V / Takelac A-5 solid content 30%) / VMCPP Laminated structure 2 : Transparent vapor-deposited PET or transparent vapor-deposited NY / Silane coupling agent + polyethyleneimine / Reverse printing ink composition / Adhesive (Takelac A-515 / Takelac A-50, solid content 30% by mass, solid content 30%) / RXC-22#60 (extrusion lamination) Laminated structure 3 : PET or NY or transparent vapor-deposited PET or transparent vapor-deposited NY / each silane coupling agent + each polyethyleneimine / each reverse printing ink composition / AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) / molten polyethylene Laminated structure 4 : OPP / each silane coupling agent + each polyethyleneimine / each reverse printing ink composition / AC agent (Epomin P-1000, solid content 0.7% by mass) / molten polyethylene
[0208] <Deinking (evaluation of ink release properties)> Deinking (evaluation of ink releasability) was carried out as follows. After printing and drying sufficiently, 1.5 g of each of the above printed matter was cut into small pieces of about 15 mm MD×25 mm TD to obtain samples for ink release property testing. (Preparation of the release solution consisting of an alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid consisting of an alkaline aqueous solution. (Preheating of the desorption solution consisting of an alkaline aqueous solution) 100 g of the alkaline aqueous solution was placed in each 200 cc HDPE (high density polyethylene) container and heated in a hot water bath until the liquid temperature reached 70°C. (Detachment) After each release liquid reached 70°C, each of the above ink removability test samples was put into each of the release liquids composed of the above alkaline aqueous solution, and using a stainless steel stirring blade with a diameter of 25 mm, in the case of the release liquid composed of the alkaline aqueous solution, it was stirred for 30 minutes. After stirring, the HDPE (high-density polyethylene) container was taken out of the water bath and allowed to stand at room temperature for 5 minutes. The release liquid and various film pieces were separated using a stainless steel mesh with an opening of approximately 2 mm. (Rinse) The various films after detachment were transferred to a 200 cc HDPE container, and 100 g of water was added. Using a stainless steel stirring blade with a diameter of 25 mm for the blade, it was stirred for 5 minutes. After standing for 5 minutes, the various film pieces and water were separated using a stainless steel mesh. After drying the various film pieces, the peelability of the ink from the various films was visually evaluated. Detachment (alkali) conditions: Stir for 30 minutes in a 2% sodium hydroxide aqueous solution at 70°C (Evaluation criteria) ○: The ink coating was completely peeled off from the resin substrate film as a coating piece ×: The ink coating did not peel off from the resin substrate film as a coating piece · For laminate structures 1 to 4, the results were the same as shown in Table 14.
[0209]
Table 14
[0210] <B. Examples of surface printing using a mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent> Except that the primer for detachment was changed to each primer composition for detachment containing the above silane coupling agent, the evaluation was carried out in the same manner as in the example of surface printing without using the above silane coupling agent. For surface printing ink compositions 1 to 8, the results were all the same as shown in Table 15.
[0211]
Table 15
[0212] <Examples of shrink printing using a mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent> The primer composition for release was evaluated in the same manner as in the examples of shrink printing without using the above silane coupling agent, except that each primer composition for release containing the above silane coupling agent was changed. For the printing ink compositions 1 and 2 for shrink packaging, the results were the same as shown in Table 16.
[0213]
Table 16
[0214] <Examples of printing on the paper substrate side of laminated paper using a mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent> The primer composition for release was evaluated in the same manner as in the examples of printing on the paper substrate of laminated paper without using the above silane coupling agent, except that each primer composition for release containing the above silane coupling agent was changed. The evaluation results are shown in Table 17.
[0215]
Table 17
[0216] <Examples and Comparative Examples Using a Siloxane-Modified Polyethyleneimine Compound> Next, the case of using a primer composition for release containing a siloxane-modified polyethyleneimine compound will be described. In the present invention, the release primer composition may contain a siloxane-modified polyethyleneimine compound from the viewpoint of adhesion. As the siloxane-modified polyethyleneimine compound, a siloxane-modified polyethyleneimine compound obtained by reacting a component containing polyethyleneimine and at least one amine-reactive hydrolyzable organosilane represented by the formula: RZ-SiY3 [wherein R represents an amine-reactive group selected from the group consisting of an isocyanate group, an oxiranyl group, a glycidoxy group, an acryloxy group, a carboethoxy group, a carbomethoxy group, a vinylsulfonyl group, and an acrylamide group, Z represents a divalent organic group containing carbon atoms, and each Y independently represents a hydrolyzable group] may be used.
[0217] <Removable primer layer> A detachment primer composition having a solid content mass % in the detachment primer composition shown in Table 18 below was applied and dried under the following conditions using a gravure printer. The application amount of the detachment primer composition in each Example in the table is the amount of solid content in the coating layer per unit area. The solid content concentration of the detachment primer composition is a concentration that becomes a siloxane-modified polyethyleneimine-based compound in the coating layer when it is made into a coating layer. (Detachment primer composition application conditions) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate (wet coating amount 6g / m 2 degree) Drying temperature: 70℃ When printing with a gravure printer, the solid content mass% of the release primer is as follows. After diluting as shown below, when printing with a gravure printer under container conditions, the following coating amount (g / m 2 ) Siloxane-modified polyethyleneimine compound: Trimethoxysilylpropyl-modified (polyethyleneimine) (product name: SSP-060, Gelest), molecular weight 1,500-1,800, amine value 10 mmol / g, amine value measured by acid titration in a non-aqueous system, amine ratio measured by NMR (13C).
[0218]
Table 18
[0219] Examples and comparative examples of printing forms in which the primer composition for desorption containing the siloxane-modified polyethyleneimine compound of the present invention is used will be described in the order of printing on the paper substrate side of reverse printing, front printing, shrink printing, a base film, and a laminated paper in which an adhesive is applied to the base film and a paper substrate is bonded. Incidentally, for the same parts of the examples and comparative examples of reverse printing, front printing, shrink printing, printing on the paper substrate side of a laminated paper in which an adhesive is applied to a base film and a paper substrate is bonded, which are printing forms using the primer composition for desorption described above that does not contain a siloxane-modified polyethyleneimine compound, description will be omitted.
[0220] <C. Examples and Comparative Examples of Reverse Printing Using a Siloxane-Modified Polyethyleneimine Compound> (Dry Lamination) · Lamination Structure 1 : P-2161#25 / Siloxane-Modified Polyethyleneimine Compound / Each Reverse Printing Ink Composition / Adhesive (Takelac A-969V / Takelac A-5 Solids Content 30%) / VMCPP · Lamination Structure 2 : Transparent Vapor Deposited PET or Transparent Vapor Deposited NY / Siloxane-Modified Polyethyleneimine Compound / Each Reverse Printing Ink Composition / Adhesive (Takelac A-515 / Takelac A-50, Solids Content 30 Mass%) Solids Content 30%) / RXC-22#60 (Extrusion Lamination) · Lamination Structure 3 : PET or NY or Transparent Vapor Deposited PET or Transparent Vapor Deposited NY / Siloxane-Modified Polyethyleneimine Compound / Each Reverse Printing Ink Composition / AC Agent (Takelac A-3210 / Takelac A-3072, Solids Content 7 Mass%) / Melt Polyethylene · Lamination Structure 4 OPP / siloxane-modified polyethyleneimine compound / printing ink composition for reverse printing / AC agent (Epomin P-1000, solid content 0.7% by mass) / molten polyethylene
[0221] <Deinking (evaluation of ink release properties)> Deinking (evaluation of ink releasability) was carried out as follows. After printing and drying sufficiently, 1.5 g of each of the above printed matter was cut into small pieces of about 15 mm MD×25 mm TD to obtain samples for ink release property testing. (Preparation of the release solution consisting of an alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid consisting of an alkaline aqueous solution. (Preheating of the desorption solution consisting of an alkaline aqueous solution) 100 g of the alkaline aqueous solution was placed in each 200 cc HDPE (high density polyethylene) container and heated in a hot water bath until the liquid temperature reached 70°C. (Detachment) After each release solution reached 70°C, each ink release test sample was placed in the release solution made of the alkaline aqueous solution, and the release solution made of the alkaline aqueous solution was stirred for 30 minutes using a stainless steel stirring blade with a diameter of 25 mm. After stirring, the HDPE (high density polyethylene) container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solution and the various film pieces were separated using a stainless steel mesh with a mesh size of approximately 2 mm. (rinse) After removal, each film was transferred to a 200cc HDPE container and 100g of water was added. The mixture was stirred for 5 minutes using a stainless steel stirring blade with a blade diameter of 25mm. After leaving the mixture to stand for 5 minutes, the film pieces were separated from the water using a stainless steel mesh. After drying the film pieces, the releasability of the ink from the films was visually evaluated. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation Criteria) ○: The ink film was completely peeled off from the resin base film as film pieces. ×: Ink film did not peel off from the resin base film as a film piece · For laminate structures 1 to 4, all had the same results as shown in Table 19
[0222]
Table 19
[0223] <Examples of surface printing using a C. siloxane-modified polyethyleneimine compound> Evaluation was carried out in the same manner as in the example of surface printing without using the above silane coupling agent, except that the primer for detachment was changed to the primer for detachment containing the above silane coupling agent-modified polyethyleneimine · For surface printing ink compositions 1 to 8, all had the same results. The results for surface printing ink composition 1 are shown in Table 20 below
[0224]
Table 20
[0225] <Examples of shrink printing using a C. siloxane-modified polyethyleneimine compound> Evaluation was carried out in the same manner as in the example of shrink printing without using the above silane coupling agent, except that the primer for detachment was changed to the primer for detachment containing the above silane coupling agent-modified polyethyleneimine · For shrink packaging printing ink compositions 1 and 2, all had the same results. The results for shrink packaging printing ink compositions 1 and 2 are shown in Table 21 below
[0226]
Table 21
[0227] <Examples of printing on the paper base material side of laminated paper using a C. siloxane-modified polyethyleneimine compound> Except for changing the release primer to the siloxane-modified polyethyleneimine-containing release primer, the same evaluation was performed as in the example of printing the laminated paper onto the paper substrate without using the silane coupling agent. The results are shown in Table 22.
[0228] [Table 22]
[0229] As shown in the results of Tables 19 to 22 above, when the primer composition of the present invention was used, the printed layer could be removed by an alkaline aqueous solution, and the laminate strength of the printed layer was sufficiently strong.
Claims
1. For forming a removable primer layer on a printed material in which a resin substrate, a removable primer layer, and a printed layer are formed in this order, A release primer composition for a resin substrate and a printing layer, the composition comprising any one of A to B below: A. Polyethyleneimine compound having an amine value of 5.0 to 25.0 mmol / g (containing no glycidyl group-containing silane coupling agent and / or no isocyanate group-containing silane coupling agent) B. A polyethyleneimine compound having an amine value of 5.0 to 25.0 mmol / g, and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent; The ratio of the sum of the number of glycidyl groups and the number of isocyanate groups of the silane coupling agent to the number of amino groups of the polyethyleneimine compound is less than 0.
20. (However, the above-mentioned detachment primer compositions A to B do not contain any binder resin other than polyethyleneimine.)
2. 2. The primer composition for detachment of a resin substrate and a printed layer according to claim 1, wherein the number average molecular weight of the polyethyleneimine compound or the siloxane-modified polyethyleneimine compound is 1,000 to 200,000.
3. 2. The primer composition for detachment of a resin substrate and a printed layer according to claim 1, wherein the polyethyleneimine compound and the siloxane-modified polyethyleneimine compound have a mass average molecular weight of 4,000 to 800,000.
4. 3. The detachment primer composition according to claim 2, wherein the number average molecular weight of the polyethyleneimine compound or the siloxane-modified polyethyleneimine compound is 1,000 to 200,000.
5. 3. The detachment primer composition according to claim 2, wherein the polyethyleneimine compound and the siloxane-modified polyethyleneimine compound have a mass average molecular weight of 4,000 to 800,000.
6. A printed matter comprising: a detachable primer layer formed from the detachable primer composition according to claim 1 or 2 on a resin substrate; and a printed layer formed on the detachable primer layer.
7. 3. A printed matter comprising: a detachable primer layer formed from the detachable primer composition according to claim 1 or 2 on a resin substrate; a paper layer formed on the detachable primer layer via an adhesive layer; and a printing layer formed on the paper layer.
Citation Information
Patent Citations
JP1988088131A
Resin for printing ink
JP1993097959A
Polyolefin sheet, and display sheet, packaging sheet, transparent sheet for recording, decorative sheet, and sheet for emblem using it
JP2001277445A
Coated film
JP2003171486A
Readily adhesive film and laminate film
JP2004123895A